Method for producing laminated film, polarizing plate, display device, and polarizing plate roll

The laminated film with a peelable functional layer on a base film, designed with specific thickness and humidity expansion coefficient relationships, addresses curling issues in thin films, improving transportability and processing productivity for polarizing plates and display devices.

JP7613464B2Active Publication Date: 2025-01-15KONICA MINOLTA INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2022511462
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-02
Publication Date
2025-01-15
Estimated Expiration
2040-04-02

AI Technical Summary

Technical Problem

Thin functional films used in liquid crystal display devices face issues with curling due to humidity fluctuations, leading to reduced transportability, lamination difficulties, and decreased yield in polarizing plate manufacturing, especially when laminated with materials having different humidity expansion coefficients.

Method used

A laminated film structure is developed where a peelable functional layer is laminated on a base film, with specific thickness and humidity expansion coefficient relationships to control curling, ensuring excellent transportability and improved processing productivity.

Benefits of technology

The laminated film maintains excellent curl controllability and processing productivity, allowing for high-quality polarizing plates with no optical unevenness, enhancing the manufacturing process and display device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613464000012
    Figure 0007613464000012
  • Figure 0007613464000013
    Figure 0007613464000013
  • Figure 0007613464000014
    Figure 0007613464000014
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a layered film which, despite being a thin film, has excellent conveyability, can be handled in the same manner as a conventional polarizing plate protective film, has excellent controllability of curling during polarizing plate processing, and has enhanced productivity (ability to be laminated with a polarizer) in polarizing plate processing; a high-quality polarizing plate that is provided with the layered film and that is devoid of optical unevenness; a display device; and a method for manufacturing a polarizing plate roll. In this layered film, a peelable functional layer is layered on a substrate film, and the layered film is characterized in that the thickness of the functional layer is in the range of 1-19 µm, the total thickness of the layered film is 50 µm or less, and the layered film satisfies the relationship represented by expression 1, where CHE1 (ppm / %RH) is the coefficient of thermal expansion of the substrate film at 23°C, d1 (µm) is the thickness of the substrate film, CHE2 (ppm / %RH) is the coefficient of thermal expansion of the functional layer at 23°C, and d2 (µm) is the thickness of the functional layer. Expression 1: 0.20 < |(CHE1 – CHE2)| × (d2 / d1) < 2.00
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate film, a polarizing plate, a display device, and a method for manufacturing a polarizing plate roll comprising the laminate film, and more specifically, to a laminate film which is thin but can be handled in the same manner as conventional polarizing plate protective films, and further has excellent curl controllability during polarizing plate processing, thereby improving the productivity of polarizing plate processing. [Background technology]

[0002] 2. Description of the Related Art Liquid crystal display devices are widely used as image display devices for televisions (TVs), personal computers (PCs), and the like, because they consume low power and can be made thin.

[0003] In recent years, there has been a demand for larger, thinner televisions and improved display quality. In order to suppress optical unevenness that occurs with stress caused by bending of the display panel and dimensional changes in the components, there is a demand for thinner components.

[0004] Furthermore, for applications such as notebook and small / medium-sized personal computers, smartphones, and slate PCs, there is a particularly high demand for thinner components, and the functional films used (e.g., viewing angle compensation films, polarizing plate protective films, etc.) need to be made even thinner.

[0005] However, if the film is made too thin, it loses its stiffness and rigidity, which causes problems such as reduced film transportability and reduced yield in the lamination process. For this reason, Patent Document 1 proposes a method in which a thin functional film is formed on a base film (also called a "carrier film") in a peelable manner, and the film is transported as a thick laminated film until lamination, and the unnecessary base film is removed after lamination with a polarizer.

[0006] However, when two films made of different materials, such as a base film and a thin functional film placed on top of it, are laminated in this way, if the materials have different humidity expansion coefficients, curling will occur due to humidity fluctuations. If the curling is very slight, it may actually make the lamination and peeling process easier, but if severe curling occurs, lamination becomes more difficult, causing a problem of reduced yield in the polarizing plate manufacturing process.

[0007] As mentioned above, Patent Document 1 discloses a method for laminating a thin functional film on a substrate film in a peelable manner in order to handle the functional film, but since there is a difference in humidity dependency between the material for forming the functional film and the substrate film, the film curls due to moisture absorption during processing of the polarizing plate or during storage, making the film difficult to handle during transport and lamination. These problems become more pronounced when the laminated film becomes thin. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-45220 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved is to provide a laminated film which, despite being thin, has excellent transportability and can be handled in the same way as conventional polarizing plate protective films, and further has excellent curl controllability during polarizing plate processing, thereby improving the productivity of polarizing plate processing (bonding ability to polarizers), and to provide a high-quality polarizing plate free of optical unevenness, a display device, and a method for manufacturing a polarizing plate roll which are equipped with the laminated film. [Means for solving the problem]

[0010] In the course of investigating the causes of the above problems in order to solve the above-mentioned problems, the present inventors discovered that a laminate film having a peelable functional layer laminated on a base film, wherein the base film and functional layer each have a thickness within a specific range, and the humidity expansion coefficient and thickness of the base film and the humidity expansion coefficient and thickness of the functional layer satisfy a specific relationship, can provide a laminate film that is thin yet has excellent transportability, can be handled in the same way as conventional polarizing plate protective films, and further has excellent curl controllability during polarizing plate processing, and has improved productivity (bonding to polarizer) in polarizing plate processing.

[0011] That is, the above-mentioned problems of the present invention are solved by the following means.

[0012] 1. A laminated film in which a peelable functional layer is laminated on a base film, The base film contains polyethylene terephthalate, The functional layer is a fumaric acid diester resin, or rubber particles (Meth)acrylic resin Fat Contains The thickness of the functional layer is within the range of 1 to 19 μm, The total thickness of the laminated film is 50 μm or less, A laminate film characterized by satisfying the relationship of the following formula (1) when the humidity expansion coefficient of the base film at 23°C is CHE1 (ppm / % RH), the thickness is d1 (μm), and the humidity expansion coefficient of the functional layer at 23°C is CHE2 (ppm / % RH), and the thickness is d2 (μm). Equation (1) 0.20<│(CHE1-CHE2)│×(d2 / d1)<2.00

[0013] 2. The laminate film described in item 1, wherein the thickness of the functional layer is within the range of 2 to 10 μm.

[0014] 3. The laminate film according to item 1 or 2, wherein the total thickness of the laminate film is within the range of 30 to 45 μm.

[0015] 4. A laminate film described in any one of items 1 to 3, characterized in that the functional layer has a retardation value Ro defined by the following formula (i) in the range of 0 to 20 nm, and a retardation value Rt defined by the following formula (ii) in the range of -25 to 25 nm. Formula (i) Ro = (n x -n y )×d Formula (ii) Rt = {(n x +n y ) / 2-n z}×d (In the above formulas (i) and (ii), Ro is the retardation value in the in-plane direction of the functional layer, Rt is the retardation value in the thickness direction of the functional layer, n x is the refractive index in the slow axis direction of the functional layer, n y is the refractive index in the fast axis direction of the functional layer, n z is the refractive index in the thickness direction of the functional layer (the refractive index is measured at a wavelength of 590 nm under an environment of 23°C and 55% RH), and d is the film thickness (nm).

[0016] 5. A laminate film described in any one of items 1 to 4, characterized in that when the residual solvent content of the base film is S1 and the residual solvent content of the functional layer is S2, the following formula (2) is satisfied. Formula (2) 10 <S1<S2<1000(ppm)

[0017] 6. The laminate film described in item 5, wherein the boiling point of a major residual solvent among the residual solvents is 100° C. or lower under atmospheric pressure.

[0018] 7. The laminate film described in item 5 or 6, wherein the residual solvent is a chlorine-based solvent.

[0019] 8. The laminate film described in any one of items 5 to 7, wherein the residual solvent is dichloromethane.

[0020] 9. The laminate film described in any one of items 5 to 8, wherein the residual solvent comprises dichloromethane and alcohols.

[0021] 10. The laminate film described in any one of items 1 to 9, characterized in that the base film is a biaxially stretched polyester film, and the humidity expansion coefficient CHE1 of the polyester film at 23°C is within the range of 10 to 20 ppm / % RH.

[0022] 11. The laminate film described in any one of items 1 to 10, wherein the functional layer contains a polymer material having a carbonyl group on the side chain.

[0023] 12. The laminate film described in any one of items 1 to 10, wherein the functional layer contains a polymer material having a cyclic structure in its main chain.

[0024] 13. A polarizing plate comprising the laminate film according to any one of items 1 to 12.

[0025] 14. A display device comprising the laminate film according to any one of items 1 to 12 or the polarizing plate according to item 13.

[0026] 15. A method for producing a polarizing plate roll, comprising: laminating the laminate film according to any one of items 1 to 12 onto at least one surface of a polarizer while winding the laminate film, From the inside of the roll, polarizer, adhesive layer, functional layer and base film M a step of winding up the laminate film while bonding it to the polarizer so as to obtain the layer order. Effect of the Invention

[0027] By the above-mentioned means of the present invention, it is possible to provide a laminate film which, although being thin, has excellent transportability, can be handled in the same way as conventional polarizing plate protective films, and further has excellent curl controllability during polarizing plate processing, improving the productivity of polarizing plate processing (bonding ability to a polarizer), as well as a high-quality polarizing plate, display device, and polarizing plate roll having the same, and a method for manufacturing the same.

[0028] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows.

[0029] When forming a laminated film (hereinafter referred to as a "laminate") in which a functional layer is arranged on a base film, warping and curling of the films to be laminated are very important factors in increasing the yield. The mechanism of warping is complex, and the mechanism by which it occurs has been unclear until now, so no method for controlling warping without sacrificing productivity had been considered.

[0030] In particular, when dealing with laminated films that have extremely thin functional layers, very little is known about predicting and improving the magnitude of curl in laminates of base films (which function as protective films) and functional layers, particularly curl that is affected by humidity.

[0031] The present inventors have investigated how the mechanism of such warpage due to humidity can be predicted and further improved by referring to a formula for predicting curl of a laminate due to heat.

[0032] Regarding curling of a laminate due to heat, the following formula has been proposed, but as a result of investigation, we have obtained an index that can accurately predict curling of a laminate under certain conditions, such as curling due to humidity fluctuation and curling in warm water, using a relatively simple formula based on the assumptions shown below.

[0033] In other words, we found that the curl of the laminate in warm water (or under high humidity) is greatly influenced by two factors: (1) the difference in the coefficient of hydroscopic expansion (CHE) between the base film and the functional layer, and (2) the thickness ratio between the base film and the functional layer.

[0034] It is known that the curl prediction formula for a bimetal laminate due to heat is expressed by the following formula (a).

[0035] Formula (a) Curl curvature 1 / R ∝ 6 (α2-α1) (ΔT) (1+m 2 ) / h[3(1+m) 2 +(1+mn){m 2 +(mn) -1}] (In the formula, α represents the thermal expansion coefficient, α1 represents the functional layer, and α2 represents the base film. ΔT represents the temperature rise width. h represents the sum of the thickness (d1) of the base film and the thickness (d2) of the functional layer. m represents the thickness ratio (d1 / d2) when the thickness (d1) of the base film is the thickness (d2) of the functional layer. n represents the elastic modulus ratio (f1 / f2) when the elastic modulus of the base film is the elastic modulus (f1) and the functional layer is the elastic modulus (f2).)

[0036] Where: 1) The difference in the humidity expansion coefficient between the base film and the functional layer is directly converted into the difference in the thermal expansion coefficient (α2-α1) = ΔCHE.

[0037] 2) When comparing various films under constant conditions, such as immersion in water, the humidity difference (ΔT) can be treated as a constant.

[0038] 3) The elastic modulus ratio n is assumed to be approximately 1, as it does not vary significantly for organic polymer materials.

[0039] 4) The thickness ratio m, which is the thickness of the base film (d1) / the thickness of the functional layer (d2), is actually the thickness of the functional layer (d2) < the thickness of the base film (d1), so 1 < <mであり、(1 / m)<<1となる。

[0040] 5) Also, the total thickness h is within a certain numerical range as a thickness that can be realistically handled and is treated as a constant.

[0041] Therefore, when the approximation conditions of the above 1) to 5) are added, Equation (a) can ultimately be expressed by Equation (f).

[0042] When "h" in Equation (a) is regarded as a constant, Equation (a) becomes Equation (b) Curl curvature 1 / R ∝ ΔCHE × (1 + m) / [3 + 3m + m 2 + m -1 When "m -1 ≈ 0" in Equation (a) is regarded as such, Equation (b) becomes Equation (c) Curl curvature 1 / R ≈ ΔCHE × (1 + m) / [3 + 3m + m 2 Equation (d) Curl curvature 1 / R ≈ ΔCHE × (1 + m) / 3(1 + m) 2 Since "m is 1 << m" in Equation (a), Equation (d) becomes Equation (e) Curl curvature 1 / R ∝ ΔCHE × 1 / (1 + m) Furthermore, since "m is 1 << m" in Equation (e), when "1 + m" is taken as "m", Equation (f) Curl curvature 1 / R ∝ ΔCHE / m That is, it was deduced that the curl curvature 1 / R can be expressed by "|(CHE1 - CHE2)| × (d2 / d1)" of Equation (1) according to the present invention, and through conducting an empirical experiment, the present invention was found.

[0043] Conceptually, it can also be understood from the qualitative phenomenon that the curl becomes more intense as the layer that swells better due to humidity is thicker.

[0044] On the other hand, it was also found that in the case of a laminate with no curl at all, it is impossible to obtain a trigger for peeling during peeling of the base film, resulting in a decrease in workability and a decrease in yield.

[0045] ​​When laminating a polarizer and a functional layer, if the humidity expansion coefficient of the base film is too large compared to that of the functional layer, the base film is likely to curl outward, causing the center of the functional layer to rise above the surface of the polarizer, making it impossible to adequately laminate the functional layer and the polarizer (see Figure 1). Furthermore, if the curl is significant, it is thought that optical unevenness is likely to occur due to internal stress in the functional layer.

[0046] In addition, when the laminated film is stored in a rolled state under high humidity, if there is a large difference in the amount of humidity expansion of each layer, this can easily cause delamination or deformation such as wrinkles in the functional layer. If delamination occurs, the transport stability is likely to decrease during transport of the laminated film or during production of a polarizing plate, and if deformation such as wrinkles occurs in the functional layer, the flatness of the functional layer is impaired, resulting in a problem that the adhesion between the functional layer and the polarizer cannot be sufficiently improved.

[0047] Therefore, the present invention has been made in consideration of the above circumstances, and it is presumed that by suppressing interlayer delamination and deformation of the functional layer during storage of the laminate film under high humidity conditions, while adjusting the humidity expansion coefficients and thicknesses of the base film and functional layer, which are factors that cause curling, to satisfy the relationship of formula (1) above, it is possible to obtain a laminate film that not only has excellent curl controllability during polarizing plate processing, but also improves the productivity of polarizing plate processing (bonding ability to polarizer) and suppresses the occurrence of optical unevenness in the functional layer.

[0048] Specifically, by making the humidity expansion coefficient of the base film and the functional layer at 23°C appropriately larger than that of the functional layer and by appropriately designing the thickness ratio of each to satisfy the range of formula (1), it is presumed that the appropriate direction and magnitude of curl of the laminated film can be controlled to improve the productivity of polarizing plate processing (adhesion to polarizer), and the effect of suppressing the occurrence of wrinkles and optical unevenness in the functional layer can be obtained. [Brief description of the drawings]

[0049] [Figure 1]A schematic diagram explaining the mechanism by which curling occurs in a high-humidity environment when a polarizing plate is produced using a peelable film laminate. [Diagram 2] Schematic diagram showing a cross section of the laminated film of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a method for producing a laminated film according to an embodiment of the present invention. [Figure 4A] Cross-sectional view of a polarizing plate with a substrate film [Figure 4B] is a cross-sectional view of a polarizing plate with the base film peeled off. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] The laminate film of the present invention is a laminate film in which a peelable functional layer is laminated on a base film, The base film contains polyethylene terephthalate, The functional layer is a fumaric acid diester resin, or rubber particles (Meth)acrylic resin Fat the thickness of the functional layer is within the range of 1 to 19 μm, the total thickness of the laminated film is 50 μm or less, and when the humidity expansion coefficient of the base film at 23° C. is CHE1 (ppm / % RH) and the thickness is d1 (μm), and the humidity expansion coefficient of the functional layer at 23° C. is CHE2 (ppm / % RH) and the thickness is d2 (μm), the relationship of the formula (1) is satisfied. This feature is a technical feature common to or corresponding to the following embodiments.

[0051] In the embodiment of the present invention, from the viewpoint of exerting the effects of the present invention, it is preferable that the thickness of the functional layer is within the range of 2 to 10 μm, from the viewpoint of suppressing wrinkles and curl deformation of the thin functional layer and providing a thinner polarizing plate when the base film is peeled off and the functional layer is attached to a polarizer, and further from the viewpoint of suppressing optical unevenness of a liquid crystal display device using the polarizing plate.

[0052] In addition, from the viewpoint of being thin but having excellent rigidity and transportability, and being able to be handled in the same manner as conventional polarizing plate protective films, the total thickness of the laminate film is preferably within the range of 30 to 45 μm.

[0053] The retardation value Ro of the functional layer defined by the formula (i) is within the range of 0 to 20 nm, and the retardation value Rt of the functional layer defined by the formula (ii) is within the range of -25 to 25 nm, which is a preferable range of retardation values ​​from the viewpoint of providing a thin polarizing plate applied to an IPS mode display device. Also, a functional layer having such optical properties is preferable from the viewpoint of using the functional layer to provide a very thin film without affecting the optical properties of various films.

[0054] When the residual solvent content of the base film is S1 and the residual solvent content of the functional layer is S2, it is preferable to satisfy the formula (2) from the viewpoint of controlling the humidity expansion coefficients (CHE1 and CHE2) of the base film and the functional layer. When the solvent also penetrates into the base film, a slight mixed layer is formed between the laminated films, which prevents the films from peeling off easily during various processes and ensures good process suitability. When a mixed solvent is used, the sum of all solvent types is used as an index.

[0055] In addition, the boiling point of the main solvent among the residual solvents is 100° C. or less under atmospheric pressure, the residual solvent is a chlorine-based solvent, and the residual solvent is dichloromethane, and among them, the residual solvent contains dichloromethane and alcohols, which are preferable from the viewpoint of ease of handling when preparing the dope for the base film and the functional layer and forming the film. By using a low boiling point solvent and a chlorine-based solvent having high solubility, the drying time after film formation can be shortened. It is estimated that a coating film with a short drying time is less dense than a coating film with a long drying time, and as a result, the permeability of moisture changes, and CHE2 can be controlled slightly. The main solvent refers to a solvent that is mixed in a ratio of more than 50 mass% in the solvent type in the coating liquid.

[0056] The base film is a biaxially stretched polyester film, and it is preferable that the humidity expansion coefficient CHE1 of the polyester film at 23° C. is within the range of 10 to 20 ppm / % RH from the viewpoint of suppressing curling of the entire laminated film by an appropriate humidity expansion coefficient CHE1. In addition, by using a biaxially stretched polyester film, the anisotropy of CHE1 is eliminated, and the occurrence of unevenness can be suppressed.

[0057] In addition, it is preferable that the functional layer contains, as the resin, a straight-chain polymer material having a carbonyl group in the side chain, or a polymer material having a cyclic structure in the main chain, from the viewpoint of controlling physical properties such as the humidity expansion coefficient and improving optical properties.

[0058] By including the laminate film of the present invention, the polarizing plate of the present invention can be processed by the same polarizing plate processing as in the past without reducing productivity or requiring a complicated processing process.

[0059] The display device of the present invention is a preferred embodiment from the viewpoint of obtaining a high-quality display device free from light leakage and optical unevenness by comprising the laminate film of the present invention or the polarizing plate of the present invention.

[0060] The method for producing a polarizing plate roll of the present invention is a method for producing a polarizing plate roll in which the laminate film of the present invention is laminated to at least one surface of a polarizer while being wound up, and the polarizer, the functional layer, and the base film are laminated from the inside of the roll. M The method for producing a polarizing plate roll includes a step of laminating the laminate film to the polarizer and winding the laminate film so that the laminate film is in the layer order of the polarizer. This method for producing a polarizing plate roll allows the base film to double as a protective film, leading to a reduction in the number of parts and a simplification of the processing steps. 。

[0061] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower limit and upper limit.

[0062] <Overview of the laminated film of the present invention> The laminate film of the present invention is a laminate film in which a peelable functional layer is laminated on a base film, The base film contains polyethylene terephthalate, The functional layer is a fumaric acid diester resin, or rubber particles (Meth)acrylic resin Fat the thickness of the functional layer is within the range of 1 to 19 μm, the total thickness of the laminated film is 50 μm or less, and when the humidity expansion coefficient of the base film at 23° C. is CHE1 (ppm / % RH) and the thickness is d1 (μm), and the humidity expansion coefficient of the functional layer at 23° C. is CHE2 (ppm / % RH) and the thickness is d2 (μm), the relationship of the following formula (1) is satisfied. Equation (1) 0.20<│(CHE1-CHE2)│×(d2 / d1)<2.00

[0063] (Measurement of coefficient of hygroscopic expansion (CHE) at 23℃) A film sample is fixed in a thermo-hygrostat so that it is 1 cm wide and 15 cm long, and dehumidified until it reaches a constant humidity (approximately 30% RH). After the film length becomes constant, it is humidified (approximately 80% RH) and begins to elongate due to moisture absorption. After approximately 24 hours, the moisture absorption reaches equilibrium and the film elongation also reaches equilibrium. The amount of elongation at this point is calculated using the formula below. During this time, the ambient temperature is kept constant at 23°C.

[0064] Humidity expansion coefficient at 23°C (ppm / %RH) = expansion amount (cm) / (sample length (cm) x humidity difference) x 10 6

[0065] As a means for controlling the coefficient of hygroscopic expansion (hereinafter, also simply referred to as "CHE"), for example, it is preferable to adjust the drying speed (film density) after the formation of the base film and the functional layer. When drying is performed at a high speed, a sparse film is likely to be formed, and the CHE becomes large.

[0066] As a means for controlling the CHE of the base film, stretching (magnification) and thermal relaxation may be used during or after film formation. When the stretching (magnification) is high, a dense film is formed and the CHE becomes small, while when thermal relaxation is performed, a coarse film is likely to be formed and the CHE becomes large, so the stretching and thermal relaxation may be used as a means for adjusting the CHE within the range of the above formula (1) in consideration of the relationship with the CHE of the functional layer.

[0067] The film-forming materials used for the base film and the functional layer are also related to the control of CHE. When the film-forming material for the functional layer is a linear polymer material having a carbonyl group in the side chain, in addition to controlling CHE, it can also have the effect of suppressing optical unevenness of the polarizer by giving it moderate moisture permeability. In particular, acrylic resins with low photoelasticity tend to exhibit good characteristics. Furthermore, it is also a preferred embodiment to use polymer materials having a cyclic structure in the main chain (e.g., cycloolefin resins) as the film-forming material, since these polymer materials have little change in optical properties due to humidity and are less likely to cause unevenness due to humidity.

[0068] When the value of the formula (1) of the laminated film is larger than 2.00, the film curls significantly, as described above, making it difficult to attach the film to the polarizing plate during production. On the other hand, when the value of the formula (1) is 0.20 or less, the base film and the functional layer are difficult to peel off, and peeling errors may occur. Therefore, it is necessary to adjust the CHE and thickness within the range of the formula (1). Furthermore, depending on the degree of curl, air bubbles or creases may occur when the film is attached to the polarizer (polyvinyl alcohol film).

[0069] The mechanism by which air bubbles are trapped during lamination is unclear, but it is believed to be as follows. If the curl is too large, the unevenness in the TD direction (width direction of the long film) becomes too large, trapping air during lamination and generating air bubbles. Conversely, if the curl is too small, the film is too susceptible to the curl in the MD direction (width direction of the long film), trapping air and generating air bubbles.

[0070] In the present invention, the curl can be controlled to a specific range to improve the lamination property. From the viewpoint of improving the lamination property, the index (|(CHE1-CHE2)|×(d2 / d1)) of the present application corresponding to the curl is in the range of more than 0.20 and less than 2.00, more preferably in the range of 0.30 to 1.00, and particularly preferably in the range of 0.40 to 0.70.

[0071] Furthermore, when the functional film is attached to a polarizer (polyvinyl alcohol film), interference fringes may occur.

[0072] Although the cause of the occurrence of interference fringes is not clear in detail, it is believed that the functional layer shrinks when the substrate film is peeled off after the laminated film of the present invention is laminated. At this time, minute refractive index irregularities occur at the interface between the polarizer and the functional layer, which is believed to be the cause of the observed interference irregularities.

[0073] It is believed that by controlling the curl within the specific range of the present invention, shrinkage unevenness of the polarizer can be made uniform and interference unevenness can be improved.

[0074] It is presumed that if the curl is too small, the effect of shrinkage of the polarizer becomes large, resulting in large interference unevenness, whereas if the curl is too large, the effect of shrinkage of the functional layer becomes large. In the present invention, from the viewpoint of interference unevenness, the index of the present application corresponding to curl (|(CHE1-CHE2)|×(d2 / d1)) is preferably in the range of 0.30 to 1.00, particularly preferably in the range of 0.40 to 0.70.

[0075] Furthermore, when the display device is provided with the functional layer, if the value of formula (1) is 2.00 or more, internal stress remains in the functional layer, and optical unevenness is likely to occur. On the other hand, if the value of formula (1) is 0.20 or less, there is a problem with the moisture permeability of the functional layer, and drying unevenness is likely to occur, and wrinkles due to drying unevenness and optical unevenness may be observed.

[0076] In addition, if the coefficient of humidity expansion CHE of the entire laminate film is large, for example, when the laminate film is stored in a rolled state at high temperatures, the difference in the amount of humidity expansion between the base film and the functional layer is likely to be large because the amount of humidity expansion of each is large. This makes it easy for delamination to occur between the base layer and the base film, or for the functional layer to deform. When delamination occurs, the transport stability of the laminate film is likely to decrease, and when the functional layer is deformed, the flatness of the functional layer is likely to be impaired, so that the adhesion to the polarizer is also likely to decrease.

[0077] In the present invention, it is preferable to reduce the humidity expansion coefficient CHE of the entire laminate film, and since the humidity expansion amount of the entire laminate film under high humidity conditions can be reduced, the difference in the humidity expansion amount between the base film and the functional layer can also be reduced. This can suppress peeling and deformation of the functional layer during storage of the laminate film under high temperatures, and can improve the adhesion to the polarizer without impairing the transport stability of the laminate film.

[0078] (Layer structure of laminated film) FIG. 2 shows an example of the layer structure of the laminated film of the present invention.

[0079] The laminated film 1 of the present invention has a base film 2 and a functional layer 3 on the base film 2. The base film 2 and the functional layer 3 may be configured by laminating a plurality of layers. In addition, the functional layer 3 may have other functional layers, such as a primer layer (not shown) or a protective layer (not shown), on the front or back surface.

[0080] The base film 2 may have an adhesive layer or pressure-sensitive adhesive layer (not shown) on the side opposite the functional layer, and the adhesive layer or pressure-sensitive adhesive layer can provide an adhesive function when the base film 2 is attached to a display element.

[0081] In this regard, the term "peelable functional layer" in the present invention refers to a mode in which the functional layer is in close contact with the base film and does not easily peel off during normal production or general use, but the functional layer can be peeled off from the base film by external stress when it is desired to use only the functional layer during polarizing plate processing.

[0082] For example, the stress when peeling the base film from the functional layer can be evaluated by, for example, using a laminate film cut to a width of 25 mm and a length of 80 mm, bonding and fixing the surface of the functional layer opposite the interface with the base film to a glass substrate via an acrylic adhesive sheet, gripping one end of the base film in the longitudinal direction of the test piece (one side with a width of 25 mm) using a tensile tester (RTF-1210 manufactured by A&D Co., Ltd.), and performing a 90° peel test (in accordance with JIS K 6854-1:1999 "Adhesives - Test method for peel adhesion strength - Part 1: 90° peel") at a crosshead speed (gripping speed) of 200 mm / min in an atmosphere of temperature 23°C and humidity 60% RH. The peel stress can be evaluated as a state in which the base film and the functional layer can be peeled off with a stress of 0.05 to 2.00 N / 25 mm. If the stress is 0.05 N / 25 mm or more, peeling is less likely to occur during the polarizing plate processing, which is preferable, and if the stress is 2.00 N / 25 mm or less, bending of the polarizing plate does not occur when the base film is peeled off, which is preferable.

[0083] The configuration of the laminated film of the present invention will be described in detail below.

[0084] [1] Base film The base film supports the functional layer and is not particularly limited as long as the difference in humidity expansion coefficient at 23° C. between the base film and the functional layer (|(CHE1-CHE2)|) can be adjusted to a range that satisfies the above formula (1). The base film usually includes a resin film.

[0085] Examples of the resin that can be used include cellulose ester resins, cycloolefin resins, polypropylene resins, acrylic resins, polyester resins, polyarylate resins, and styrene resins or composite resins thereof. Among these, it is preferable to use polyester resins, which have an appropriately large humidity expansion coefficient and are easy to control within the range of formula (1).

[0086] Examples of resin films include polyester-based resins (e.g., polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), etc.). Among these, polyester-based resin films containing polyethylene terephthalate (PET) or polyethylene naphthalate (PEN) are preferred because the humidity expansion coefficient CHE at 23°C of the laminated film is easily adjusted to fall within the range of the above formula (1).

[0087] The resin film may be one that has been heat-treated (heat-relaxed) or stretched, and is suitably used to control CHE as described above.

[0088] The heat treatment can increase the humidity expansion coefficient CHE1 of the resin film and, in turn, the base film, since it reduces the residual stress (e.g., residual stress due to stretching) of the resin film. The heat treatment temperature is not particularly limited, but can be performed at (Tg+60) to (Tg+180)°C, where Tg is the glass transition temperature of the resin constituting the resin film.

[0089] The stretching treatment increases the residual stress of the resin film, and therefore can reduce the humidity expansion coefficient CHE1 of the resin film and, in turn, the base film. The stretching treatment is preferably performed, for example, in two axial directions of the resin film. The stretching treatment can be performed under any conditions, for example, at a stretching ratio of about 120 to 900%. Whether the resin film is stretched can be confirmed, for example, by whether there is an in-plane slow axis (an axis extending in the direction in which the refractive index is maximized). The stretching treatment may be performed before or after laminating the functional layer, but it is preferable to stretch the resin film before laminating.

[0090] The polyester-based resin film (also simply referred to as polyester film) may be a commercially available product, and for example, polyethylene terephthalate film TN100 (manufactured by Toyobo Co., Ltd.) or MELINEX ST504 (manufactured by Teijin DuPont Films Co., Ltd.) may be suitably used.

[0091] The substrate film may further have a release layer provided on the surface of the resin film. The release layer can facilitate peeling of the functional layer from the substrate film when producing a polarizing plate.

[0092] The release layer may contain a known release agent and is not particularly limited. Examples of the release agent contained in the release layer include silicone-based release agents and non-silicone-based release agents.

[0093] Examples of silicone-based release agents include known silicone-based resins.Examples of non-silicone-based release agents include long-chain alkyl pendant polymers that react long-chain alkyl isocyanate with polyvinyl alcohol or ethylene-vinyl alcohol copolymers, olefin resins (e.g., copolymerized polyethylene, cyclic polyolefin, polymethylpentene), polyarylate resins (e.g., polycondensates of aromatic dicarboxylic acid components and dihydric phenol components), fluorine resins (e.g., polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), PFA (copolymer of tetrafluoroethylene and perfluoroalkoxyethylene), FEP (copolymer of tetrafluoroethylene and hexafluoropropylene), ETFE (copolymer of tetrafluoroethylene and ethylene)).

[0094] The thickness of the release layer is not particularly limited as long as it is sufficient to exhibit the desired releasability, but it is preferably, for example, 0.1 to 1.0 μm.

[0095] Furthermore, if the humidity expansion coefficient of the base film itself at 23° C. is within the range of 10 to 20 ppm / % RH, warping is unlikely to occur, which is preferable.

[0096] This is presumably because, if the RH is 10 ppm / % or more, the substrate film can follow the fluctuation of the polarizer due to environmental changes, and as a result, the occurrence of defective appearance can be avoided, whereas, if the RH is 20 ppm / % or less, humidity expansion of the substrate film itself can be avoided, and as a result, the occurrence of warping can be suppressed.

[0097] (Thickness) The total thickness of the laminated film of the present invention is 50 μm or less, and preferably in the range of 30 to 45 μm. The thickness d1 of the base film is thin but needs a certain degree of strength (flexibility and rigidity) as a support, so that it is preferably in the range of 15 to 45 μm, and more preferably in the range of 20 to 40 μm.

[0098] [1.2] Additives <Plasticizer> The base film according to the present invention may contain a plasticizer. The plasticizer is not particularly limited, but is preferably selected from polyhydric alcohol ester plasticizers, phthalate ester plasticizers, citric acid plasticizers, fatty acid ester plasticizers, phosphate ester plasticizers, polycarboxylic acid ester plasticizers, polyester plasticizers, and the like.

[0099] <Ultraviolet absorber> The substrate film according to the present invention may also contain an ultraviolet absorbing agent. Examples of the ultraviolet absorbing agent used include benzotriazole-based, 2-hydroxybenzophenone-based, and salicylic acid phenyl ester-based agents. For example, triazoles such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, and 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, and benzophenones such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 2,2′-dihydroxy-4-methoxybenzophenone can be exemplified.

[0100] <Antioxidants> The substrate film according to the present invention may contain an antioxidant, which is also called an anti-deterioration agent.

[0101] Antioxidants have the role of delaying or preventing decomposition of the base film due to, for example, halogens contained in residual solvents in the base film or phosphoric acid in phosphate-based plasticizers, and so are preferably contained in the base film.

[0102] As such an antioxidant, a hindered phenol compound is preferably used, and for example, 2,6-di-t-butyl-p-cresol, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], or triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate] is preferred.

[0103] <Fine particles> The substrate film according to the present invention preferably contains fine particles.

[0104] As the fine particles used in the present invention, examples of inorganic compounds include silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate.Fine particles of organic compounds can also be preferably used.Examples of organic compounds include polytetrafluoroethylene, cellulose acetate, polystyrene, polymethyl methacrylate, polypropyl methacrylate, polymethyl acrylate, polyethylene carbonate, acrylic styrene resins, silicone resins, polycarbonate resins, benzoguanamine resins, melamine resins, polyolefin powders, polyester resins, polyamide resins, polyimide resins, or polyethylene fluoride resins, pulverized fractions of organic polymer compounds such as starch, and polymer compounds synthesized by suspension polymerization.

[0105] The fine particles preferably contain silicon because they have a lower turbidity, and silicon dioxide is particularly preferred. For example, Aerosil R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, and TT600 (all manufactured by Nippon Aerosil Co., Ltd.) are commercially available and can be used.

[0106] [1.3] Method for manufacturing base film The substrate film according to the present invention can be produced by a conventional method such as inflation, T-die, calendar, cutting, casting, emulsion, or hot press, but the solution casting and melt casting methods are preferred from the viewpoints of suppressing coloration, foreign matter defects, and optical defects such as die lines. The solution casting method uses a low temperature during processing, and therefore can provide high functionality by using various additives. In addition, the solution casting method can also control the residual solvent content of the substrate film in order to adjust CHE1. The "solution casting method" will be described below.

[0107] <Solution casting method> In the case of forming a film by the solution casting method, the method of manufacturing the substrate film according to the present invention preferably includes the steps of dissolving and dispersing a thermoplastic resin and additives such as the above-mentioned fine particles in a solvent to prepare a dope (dissolving step; dope preparation step), casting the dope onto an endless metal support that moves indefinitely (casting step), drying the cast dope as a web (solvent evaporation step), peeling it off from the metal support (peeling step), drying, stretching, and width retention steps (stretching, width retention, drying step), and winding the finished film into a roll (winding step). The solvent used in the dope preparation step of the solution casting method can be appropriately selected from the solvents used in the formation of the functional layer described below.

[0108] The content of the residual solvent in the web at the time of peeling the web (hereinafter also referred to as "residual solvent amount") is appropriately adjusted depending on the strength of the drying conditions, the length of the metal support, etc. In order for the film to exhibit good flatness, the residual solvent amount at the time of peeling the web from the metal support is preferably 10 to 150% by mass. If peeling is performed at a time when the residual solvent amount is greater, if the web is too soft, the flatness at the time of peeling is impaired and wrinkles or vertical streaks due to peeling tension are likely to occur, so the residual solvent amount at the time of peeling is determined taking into account the balance between economic speed and quality. It is more preferably 10 to 40% by mass or 60 to 130% by mass, and particularly preferably 10 to 30% by mass or 70 to 120% by mass.

[0109] In the present invention, the residual solvent amount in the base film is defined by the following formula.

[0110] Residual solvent amount (mass%) = [(MN) / N] x 100 Here, M is the mass of a sample taken at any time during or after the production of the web or film, and N is the mass of M after heating for 1 hour at 115° C. Note that the residual solvent type is basically the solvent type used, but can be appropriately measured and identified by gas chromatography or the like.

[0111] In the drying, stretching and width holding process, the film is generally dried by a roll drying method (a method in which the web is alternately passed through multiple rollers arranged above and below to dry) or a tenter method in which the web is transported while being dried. For example, after peeling, the web is dried using a drying device in which the web is alternately passed through multiple rollers arranged inside the drying device to be transported, and / or a tenter stretching device in which both ends of the web are clipped with clips and transported.

[0112] The means for drying the web is not particularly limited, and generally includes hot air, infrared rays, a heated roller, microwaves, etc., but from the viewpoint of simplicity, it is preferable to use hot air.

[0113] It is preferable to stretch the web in at least one direction. The orientation of the molecules in the film can be controlled by stretching. In particular, the anisotropy of CHE1 can be eliminated by biaxial stretching as described below, and the occurrence of unevenness can be suppressed.

[0114] As a specific stretching method, the film may be biaxially stretched or uniaxially stretched sequentially or simultaneously in the longitudinal direction (film-forming direction; casting direction; MD direction) of the web and the direction perpendicular to the web surface, i.e., the width direction (TD direction). A biaxially stretched film is preferably obtained by performing biaxial stretching in the casting direction (MD direction) and the width direction (TD direction). The stretching operation may be divided into multiple stages. When performing biaxial stretching, simultaneous biaxial stretching may be performed or may be performed stepwise. Simultaneous biaxial stretching also includes a case where the film is stretched in one direction and the other direction is shrunk by relaxing the tension.

[0115] The final stretching ratio in the two mutually perpendicular axial directions is preferably 0.8 to 1.5 times in the casting direction and 1.1 to 2.5 times in the width direction, and more preferably 0.8 to 1.2 times in the casting direction and 1.2 to 2.0 times in the width direction.

[0116] The stretching temperature is usually preferably within the range of Tg of the resin constituting the film to Tg+60° C. In general, the stretching temperature is preferably 120° C. to 200° C., and more preferably 120° C. to 180° C.

[0117] The amount of residual solvent in the web during stretching is preferably 0 to 20% by mass, and more preferably 0 to 15% by mass.

[0118] There is no particular limitation on the method of stretching the web. For example, a method of stretching the web in the longitudinal direction by using the difference in peripheral speed between a plurality of rollers, a method of fixing both ends of the web with clips or pins and stretching the web in the longitudinal direction by widening the interval between the clips or pins in the traveling direction, a method of similarly widening the web in the lateral direction and stretching the web in the lateral direction, or a method of simultaneously widening the web in the longitudinal and lateral directions and stretching the web in both the longitudinal and lateral directions. Of course, these methods may be used in combination. Among them, it is particularly preferable to stretch the web in the width direction (lateral direction) by a tenter method in which both ends of the web are held by clips or the like. It is preferable to hold the web in the width direction or stretch the web in the lateral direction in the film-forming process by using a tenter, which may be a pin tenter or a clip tenter.

[0119] The substrate film according to the present invention can obtain the same effect by heat relaxing instead of stretching. The heat relaxing is usually performed at a temperature range of Tg to Tg+60°C of the resin constituting the film. The heat relaxing temperature is usually preferably 120°C to 200°C, more preferably 120°C to 180°C.

[0120] The film is then wound into a roll by a winding process. The film may be wound by any commonly used method, such as a constant torque method, a constant tension method, a taper tension method, or a program tension control method with constant internal stress, and any of these may be used appropriately.

[0121] The substrate film according to the present invention is preferably a long film, specifically, about 100 m to 10,000 m, and is usually provided in a roll form. The longer the film length, the more the amount that can be produced in one production run, so it is preferable. From the viewpoint of transportability and handling, a compact roll form is required, so the total thickness of the laminated film is preferably thin.

[0122] [2] Functional layer The functional layer according to the present invention is peeled off from the substrate film and then attached to a polarizer, or is peeled off after being attached to a polarizer to form a polarizing plate, and can function as an optical film such as a polarizing plate protective film or a retardation film.

[0123] The thickness of the functional layer according to the present invention is within the range of 1 to 19 μm, and preferably within the range of 2 to 10 μm, from the viewpoints of providing a thin polarizing plate and simultaneously suppressing wrinkles and curl deformation of the thin functional layer.

[0124] [2.1] Resin The resin used in the functional layer according to the present invention is not particularly limited, but it is preferable to contain a linear polymer material having a carbonyl group in the side chain or a polymer material having a cyclic structure in the main chain in order to control the humidity expansion coefficient. Therefore, preferred resins may be cycloolefin resins, fumaric acid diester resins, (meth)acrylic resins, or styrene-(meth)acrylate copolymers.

[0125] <Cycloolefin Resin> The cycloolefin resin used in the functional layer is preferably a polymer of a cycloolefin monomer, or a copolymer of a cycloolefin monomer and another copolymerizable monomer.

[0126] The cycloolefin monomer is preferably a cycloolefin monomer having a norbornene skeleton, and more preferably a cycloolefin monomer having a structure represented by the following general formula (A-1) or (A-2).

[0127] [ka]

[0128] In general formula (A-1), R 1 ~R 4 each independently represents a hydrogen atom, a hydrocarbon group having 1 to 30 carbon atoms, or a polar group, and p represents an integer of 0 to 2. 1 ~R 4 Not all of these represent hydrogen atoms at the same time, and R 1 and R 2 does not simultaneously represent a hydrogen atom, and R 3 and R 4 does not simultaneously represent a hydrogen atom.

[0129] In general formula (A-1), R 1 ~R 4The hydrocarbon group having 1 to 30 carbon atoms represented by the formula (I) is preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 5 carbon atoms. The hydrocarbon group having 1 to 30 carbon atoms may further have a linking group containing, for example, a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, or a silicon atom. Examples of such linking groups include divalent polar groups such as a carbonyl group, an imino group, an ether bond, a silyl ether bond, and a thioether bond. Examples of the hydrocarbon group having 1 to 30 carbon atoms include a methyl group, an ethyl group, a propyl group, and a butyl group.

[0130] In general formula (A-1), R 1 ~R 4 Examples of the polar group represented by the formula (I) include a carboxy group, a hydroxy group, an alkoxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amide group, and a cyano group. Among them, a carboxy group, a hydroxy group, an alkoxycarbonyl group, and an aryloxycarbonyl group are preferred, and an alkoxycarbonyl group and an aryloxycarbonyl group are preferred from the viewpoint of ensuring solubility during solution casting.

[0131] In the general formula (A-1), p is preferably 1 or 2 from the viewpoint of improving the heat resistance of the optical film. When p is 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is easily improved. In addition, there is an advantage that the polymer becomes slightly responsive to humidity, making it easier to control the curl balance of the laminate.

[0132] [ka]

[0133] In general formula (A-2), R 5 R represents a hydrogen atom, a hydrocarbon group having 1 to 5 carbon atoms, or an alkylsilyl group having an alkyl group having 1 to 5 carbon atoms. 6represents a carboxy group, a hydroxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amido group, a cyano group, or a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom). p represents an integer of 0 to 2.

[0134] R in general formula (A-2) 5 preferably represents a hydrocarbon group having 1 to 5 carbon atoms, and more preferably represents a hydrocarbon group having 1 to 3 carbon atoms.

[0135] R in general formula (A-2) 6 preferably represents a carboxy group, a hydroxy group, an alkoxycarbonyl group or an aryloxycarbonyl group, and more preferably an alkoxycarbonyl group or an aryloxycarbonyl group from the viewpoint of ensuring solubility during solution casting.

[0136] In terms of improving the heat resistance of the optical film, p in general formula (A-2) preferably represents 1 or 2. When p represents 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is likely to be improved.

[0137] Cycloolefin monomers having a structure represented by general formula (A-2) are preferred from the viewpoint of improving solubility in organic solvents. In general, by breaking the symmetry of an organic compound, the crystallinity is reduced, and the solubility in organic solvents is improved. R in general formula (A-2) 5 and R 6 is substituted only on the ring carbon atom on one side of the axis of symmetry of the molecule, so that the molecular symmetry is low. In other words, a cycloolefin monomer having a structure represented by general formula (A-2) has high solubility and is therefore suitable for producing an optical film by a solution casting method.

[0138] The content ratio of the cycloolefin monomer having the structure represented by general formula (A-2) in the polymer of the cycloolefin monomer can be, for example, 70 mol% or more, preferably 80 mol% or more, more preferably 100 mol% based on the total of all the cycloolefin monomers constituting the cycloolefin resin. If the cycloolefin monomer having the structure represented by general formula (A-2) is contained at a certain level or more, the orientation of the resin is increased, so that the retardation value is likely to increase.

[0139] Specific examples of cycloolefin monomers having a structure represented by general formula (A-1) are shown in Exemplary Compounds 1 to 14 below, and specific examples of cycloolefin monomers having a structure represented by general formula (A-2) are shown in Exemplary Compounds 15 to 34 below.

[0140] [ka]

[0141] Examples of the copolymerizable monomer copolymerizable with the cycloolefin monomer include a copolymerizable monomer capable of ring-opening copolymerization with the cycloolefin monomer, and a copolymerizable monomer capable of addition copolymerization with the cycloolefin monomer.

[0142] Examples of copolymerizable monomers capable of ring-opening copolymerization include cycloolefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, and dicyclopentadiene.

[0143] Examples of copolymerizable monomers capable of addition copolymerization include unsaturated double bond-containing compounds, vinyl cyclic hydrocarbon monomers, and (meth)acrylates. Examples of unsaturated double bond-containing compounds include olefin compounds having 2 to 12 carbon atoms (preferably 2 to 8), examples of which include ethylene, propylene, and butene. Examples of vinyl cyclic hydrocarbon monomers include vinylcyclopentene monomers such as 4-vinylcyclopentene and 2-methyl-4-isopropenylcyclopentene. Examples of (meth)acrylates include alkyl (meth)acrylates having 1 to 20 carbon atoms, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.

[0144] The content of the cycloolefin monomer in the copolymer of a cycloolefin monomer and a copolymerizable monomer can be, for example, 20 to 80 mol %, preferably 30 to 70 mol %, based on the total of all monomers constituting the copolymer.

[0145] As described above, the cycloolefin resin is a polymer obtained by polymerizing or copolymerizing a cycloolefin monomer having a norbornene skeleton, preferably a cycloolefin monomer having a structure represented by general formula (A-1) or (A-2), and examples thereof include the following:

[0146] 1) Ring-opening polymers of cycloolefin monomers 2) Ring-opening copolymers of cycloolefin monomers and copolymerizable monomers capable of ring-opening copolymerization with the cycloolefin monomers. 3) Hydrogenated products of the ring-opening (co)polymers of 1) or 2) above 4) A (co)polymer obtained by cyclizing the ring-opened (co)polymer of 1) or 2) above by the Friedel-Crafts reaction and then hydrogenating the same. 5) Saturated copolymers of cycloolefin monomers and compounds containing unsaturated double bonds 6) Addition copolymers of cycloolefin monomers with vinyl cyclic hydrocarbon monomers and their hydrogenated products 7) Alternating copolymer of cycloolefin monomer and (meth)acrylate

[0147] The polymers 1) to 7) above can be obtained by known methods, for example, the methods described in JP-A-2008-107534 and JP-A-2005-227606. For example, the catalyst and solvent used in the ring-opening copolymerization 2) above can be those described in paragraphs 0019 to 0024 of JP-A-2008-107534. The catalyst used in the hydrogenation 3) and 6) above can be those described in paragraphs 0025 to 0028 of JP-A-2008-107534. The acidic compound used in the Friedel-Crafts reaction 4) above can be those described in paragraph 0029 of JP-A-2008-107534. The catalyst used in the addition polymerization 5) to 7) above can be those described in paragraphs 0058 to 0063 of JP-A-2005-227606. The alternating copolymerization reaction of 7) above can be carried out, for example, by the method described in paragraphs 0071 and 0072 of JP-A No. 2005-227606.

[0148] Among them, the polymers of 1) to 3) and 5) above are preferred, and the polymers of 3) and 5) above are more preferred. That is, the cycloolefin resin preferably contains at least one of a structural unit represented by the following general formula (B-1) and a structural unit represented by the following general formula (B-2) from the viewpoint of increasing the glass transition temperature and light transmittance of the resulting cycloolefin resin, and preferably contains only a structural unit represented by the general formula (B-2) or More preferably, the structural unit represented by the general formula (B-1) contains both a structural unit represented by the general formula (B-2) and a structural unit represented by the general formula (B-1). The structural unit represented by the general formula (B-1) is a structural unit derived from a cycloolefin monomer represented by the general formula (A-1) described above, and the structural unit represented by the general formula (B-2) is a structural unit derived from a cycloolefin monomer represented by the general formula (A-2) described above.

[0149] [ka]

[0150] In the general formula (B-1), X represents -CH=CH- or -CH2CH2-. 1 ~R 4 and p are each R in general formula (A-1). 1 ~R 4 and p.

[0151] [ka]

[0152] In the general formula (B-2), X represents -CH=CH- or -CH2CH2-. 5 ~R 6 and p are each R in general formula (A-2). 5 ~R 6 and p.

[0153] The cycloolefin resin according to the present invention may be a commercially available product. Examples of commercially available cycloolefin resins include Arton G (e.g., G7810, etc.), Arton F, Arton R (e.g., R4500, R4900, and R5000, etc.), and Arton RX (e.g., RX4500, etc.) manufactured by JSR Corporation.

[0154] The intrinsic viscosity [η]inh of cycloolefin resin is 0.2 to 5 cm when measured at 30°C. 3 / g, and 0.3 to 3 cm 3 / g is more preferable, and 0.4 to 1.5 cm 3 It is more preferable that the molecular weight is / g.

[0155] The number average molecular weight (Mn) of the cycloolefin resin is preferably 8,000 to 100,000, more preferably 10,000 to 80,000, and even more preferably 12,000 to 50,000. The weight average molecular weight (Mw) of the cycloolefin resin is preferably 20,000 to 300,000, more preferably 30,000 to 250,000, and even more preferably 40,000 to 200,000. The number average molecular weight and weight average molecular weight of the cycloolefin resin can be measured in polystyrene equivalent terms by gel permeation chromatography (GPC).

[0156] <Gel permeation chromatography> Solvent: Methylene chloride Column: Shodex K806, K805, K803G (Showa Denko K.K., three columns connected together) Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0mL / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) in the range of Mw=500 to 2,800,000. It is preferable to use the 13 samples at approximately equal intervals.

[0157] When the intrinsic viscosity [η]inh, number average molecular weight and weight average molecular weight are within the above ranges, the cycloolefin resin has good heat resistance, water resistance, chemical resistance, mechanical properties and moldability as a functional layer.

[0158] The glass transition temperature (Tg) of the cycloolefin resin is usually 110° C. or higher, preferably 110 to 350° C., more preferably 120 to 250° C., and even more preferably 120 to 220° C. If the Tg is 110° C. or higher, deformation under high temperature conditions is easily suppressed. On the other hand, if the Tg is 350° C. or lower, molding is easy and deterioration of the resin due to heat during molding is also easily suppressed.

[0159] The content of the cycloolefin resin is preferably 70% by mass or more, and more preferably 80% by mass or more, based on the functional layer.

[0160] <Fumaric acid diester resin> The fumaric acid diester resin used in the functional layer is a fumaric acid diester resin containing a diisopropyl fumarate residue unit and a fumaric acid diester residue unit having an alkyl group having 1 or 2 carbon atoms.

[0161] Here, the alkyl groups having 1 or 2 carbon atoms in the fumaric acid diester residue unit having an alkyl group having 1 or 2 carbon atoms are each independent, and examples thereof include a methyl group and an ethyl group. These may be substituted with a halogen group such as fluorine or chlorine; an ether group; an ester group, or an amino group. Examples of the fumaric acid diester residue unit having an alkyl group having 1 or 2 carbon atoms include a dimethyl fumarate residue unit and a diethyl fumarate residue unit. These may be contained in one or more kinds.

[0162] Specific examples of fumaric acid diester resins include diisopropyl fumarate / dimethyl fumarate copolymer resins, diisopropyl fumarate / diethyl fumarate copolymer resins, and the like.

[0163] The fumaric acid diester resin may contain other monomer residue units as long as the residue units do not exceed the scope of the present invention. Examples of other monomer residue units include styrene residue units such as a styrene residue unit and an α-methylstyrene residue unit; (meth)acrylic acid residue units; (meth)acrylic acid ester residue units such as a methyl (meth)acrylate residue unit, an ethyl (meth)acrylate residue unit and a butyl (meth)acrylate residue unit; vinyl ester residue units such as a vinyl acetate residue unit and a vinyl propionate residue unit; an acrylonitrile residue unit; a methacrylonitrile residue unit; and methyl vinyl ether. residue unit, an ethyl vinyl ether residue unit, a butyl vinyl ether residue unit, and the like; N-substituted maleimide residue units, such as an N-methylmaleimide residue unit, an N-cyclohexylmaleimide residue unit, and an N-phenylmaleimide residue unit; olefin residue units, such as an ethylene residue unit, a propylene residue unit, and the like; or fumaric acid diester residues other than the fumaric acid diester residue units, such as a di-n-butyl fumarate residue unit, a bis(2-ethylhexyl) fumarate residue unit, and cinnamic acid and a cinnamic acid ester unit, can be mentioned as one or more selected from the group consisting of cinnamic acid and cinnamic acid ester units.

[0164] The blending ratio of the fumaric acid diester resin used in the present invention is preferably 50 to 99 mol % of diisopropyl fumarate residue units and 1 to 50 mol % of fumaric acid diester residue units having an alkyl group having 1 or 2 carbon atoms, and is preferably 60 to 95 mol % of diisopropyl fumarate residue units and 5 to 40 mol % of fumaric acid diester residue units having an alkyl group having 1 or 2 carbon atoms, because the retardation properties and strength of the retardation film produced by the process are excellent. Fumaric acid diester resins are particularly preferred.

[0165] The fumaric acid diester resin used in the present invention preferably has a number average molecular weight in the range of 50,000 to 250,000 in terms of standard polystyrene obtained from an elution curve measured by the gel permeation chromatography.

[0166] (Example of synthesis of fumaric acid diester resin) In a 1L autoclave equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, 2g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name Metolose 60SH-50), 600g of distilled water, 330g of diisopropyl fumarate, 70g of diethyl fumarate, and 3g of t-butyl peroxypivalate as a polymerization initiator were placed, and after nitrogen bubbling for 1 hour, radical suspension polymerization was carried out by maintaining the mixture at 50°C for 24 hours while stirring at 400 rpm. The mixture was cooled to room temperature, and the suspension containing the generated polymer particles was filtered and washed with distilled water and methanol to obtain a fumaric acid diester resin (yield: 75%).

[0167] The number average molecular weight of the obtained fumaric acid diester resin was 120000. In addition, it was confirmed by 1H-NMR measurement that the resin composition was diisopropyl fumarate residue units / diethyl fumarate residue units=84 / 16 (mol %).

[0168] (Meth)acrylic resin The (meth)acrylic resin used in the functional layer preferably contains at least a structural unit (U1) derived from methyl methacrylate and a structural unit (U2) derived from phenylmaleimide. The (meth)acrylic resin containing the structural unit (U2) derived from phenylmaleimide can reduce the humidity expansion coefficient CHE2 of the functional layer. In addition, the photoelastic coefficient is also reduced, which has the advantage that unevenness is less likely to occur even if the functional layer expands due to moisture absorption.

[0169] The (meth)acrylic resin may further contain other structural units than those mentioned above. Examples of such other structural units include (meth)acrylic acid alkyl esters such as adamantyl acrylate; (meth)acrylic acid cycloalkyl esters such as 2-ethylhexyl acrylate. Among them, it is preferable to further contain a structural unit (U3) derived from an acrylic acid alkyl ester from the viewpoint of reducing the deterioration of brittleness caused by the inclusion of the structural unit (U2) derived from phenylmaleimide.

[0170] That is, the (meth)acrylic resin more preferably contains a structural unit (U1) derived from methyl methacrylate, a structural unit (U2) derived from phenylmaleimide, and a structural unit (U3) derived from an alkyl acrylate.

[0171] The content of the structural unit (U1) derived from methyl methacrylate is preferably from 50 to 95 mass %, and more preferably from 70 to 90 mass %, based on all structural units constituting the (meth)acrylic resin.

[0172] The structural unit (U2) derived from phenylmaleimide has a relatively rigid structure, and therefore can reduce the humidity expansion coefficient CHE2 of the functional layer. In addition, the structural unit (U2) derived from phenylmaleimide has a relatively bulky structure, and therefore can have microvoids that can move rubber particles in the resin matrix, and therefore can make it easier for the rubber particles to be unevenly distributed in the surface layer portion of the functional layer.

[0173] The content of the structural unit (U2) derived from phenylmaleimide is preferably 1 to 25% by mass based on the total structural units constituting the (meth)acrylic resin. When the content of the structural unit (U2) derived from phenylmaleimide is 1% by mass or more, the humidity expansion coefficient CHE2 at 23°C of the functional layer is easily reduced, and when it is 25% by mass or less, the brittleness of the functional layer is not excessively impaired. From the above viewpoint, the content of the structural unit (U2) derived from phenylmaleimide is more preferably 7 to 15% by mass.

[0174] The structural unit (U3) derived from an alkyl acrylate can impart appropriate flexibility to the resin, and can therefore improve the brittleness caused by including, for example, the structural unit (U2) derived from a phenylmaleimide.

[0175] The alkyl acrylate is preferably an alkyl acrylate having an alkyl moiety with 1 to 7 carbon atoms, preferably 1 to 5. Examples of the alkyl acrylate include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, hexyl acrylate, and 2-ethylhexyl acrylate.

[0176] The content of the structural unit (U3) derived from an acrylic acid alkyl ester is preferably 1 to 25% by mass based on the total structural units constituting the (meth)acrylic resin. When the content of the structural unit (U3) derived from an acrylic acid alkyl ester is 1% by mass or more, the (meth)acrylic resin can be given an appropriate flexibility, so that the functional layer does not become too brittle and is difficult to break. When the content of the structural unit (U3) derived from an acrylic acid alkyl ester is 25% by mass or less, the Tg of the functional layer does not become too low, and the humidity expansion coefficient (CHE2) at 23°C does not become too large. From the above viewpoint, the content of the structural unit (U3) derived from an acrylic acid alkyl ester is more preferably 5 to 15% by mass.

[0177] The ratio of the structural unit (U2) derived from phenylmaleimide to the total amount of the structural unit (U2) derived from phenylmaleimide and the structural unit (U3) derived from an alkyl acrylate is preferably 20 to 70% by mass. If the ratio is 20% by mass or more, the tensile modulus G2 of the functional layer is easily increased, and if it is 70% by mass or less, the functional layer does not become too brittle.

[0178] The glass transition temperature (Tg) of the (meth)acrylic resin is preferably 100° C. or higher, and more preferably 120 to 150° C. When the Tg of the (meth)acrylic resin is within the above range, the heat resistance of the functional layer is easily improved. In order to adjust the Tg of the (meth)acrylic resin, it is preferable to adjust the content of, for example, the structural unit (U2) derived from phenylmaleimide or the structural unit (U3) derived from an alkyl acrylate.

[0179] The weight average molecular weight (Mw) of the (meth)acrylic resin is not particularly limited and can be adjusted according to the purpose. The weight average molecular weight of the (meth)acrylic resin is preferably 100,000 or more, more preferably 1,000,000 or more, from the viewpoint of, for example, promoting entanglement between resin molecules to increase the toughness of the functional layer and make it difficult to break, and from the viewpoint of appropriately increasing the CHE ratio and making it easy to adjust the curl amount to a level preferable for adhesion. When the weight average molecular weight of the (meth)acrylic resin is 1,000,000 or more, the toughness of the resulting functional layer can be increased. Thereby, when conveying to the laminated film, it is possible to suppress the functional layer from breaking due to conveying tension, and conveying stability can be improved. From the same viewpoint, the weight average molecular weight of the (meth)acrylic resin is more preferably 1,500,000 to 3,000,000. The method for measuring the weight average molecular weight is as described above.

[0180] Styrene / (meth)acrylate copolymer Styrene-(meth)acrylate copolymers (hereinafter referred to as styrene-acrylic resins) have excellent transparency when used in functional layers. In addition, the moisture absorption expansion coefficient can be adjusted by the copolymerization ratio of the styrene portion, so curling of the laminate can be controlled by changing these ratios.

[0181] Styrene-acrylic resins are formed by addition polymerization of at least styrene monomer and (meth)acrylic acid ester monomer. Styrene monomers include styrene, which has the structural formula CH2=CH-C6H5, as well as styrene derivatives that have known side chains or functional groups in the styrene structure.

[0182] In addition, the (meth)acrylic acid ester monomer includes acrylic acid esters and methacrylic acid esters represented by CH(R1)=CHCOOR2 (R1 represents a hydrogen atom or a methyl group, and R2 represents an alkyl group having 1 to 24 carbon atoms), as well as acrylic acid ester derivatives and methacrylic acid ester derivatives having known side chains or functional groups in the structure of these esters.

[0183] Examples of styrene monomers include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene.

[0184] Examples of the (meth)acrylic acid ester monomer include acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate (2EHA), stearyl acrylate, lauryl acrylate, and phenyl acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate.

[0185] In this specification, the term "(meth)acrylic acid ester monomer" is a general term for "acrylic acid ester monomer" and "methacrylic acid ester monomer" and means one or both of them. For example, "methyl (meth)acrylate" means one or both of "methyl acrylate" and "methyl methacrylate".

[0186] The (meth)acrylic acid ester monomer may be one or more kinds. For example, it is possible to form a copolymer using a styrene monomer and two or more kinds of acrylic acid ester monomers, to form a copolymer using a styrene monomer and two or more kinds of methacrylic acid ester monomers, or to form a copolymer using a styrene monomer, an acrylic acid ester monomer, and a methacrylic acid ester monomer in combination.

[0187] The weight average molecular weight (Mw) of the styrene-acrylic resin is preferably within a range of 5,000 to 150,000, and more preferably within a range of 10,000 to 70,000, from the viewpoint of easy control of plasticity.

[0188] The styrene-acrylic resin according to the present invention may be a commercially available product, and an example thereof is MS resin "TX320XL" manufactured by Denka Co., Ltd.

[0189] <Polyarylate Resin> The polyarylate resin has excellent toughness when used in the functional layer, and contains at least a structural unit derived from an aromatic dialcohol and a structural unit derived from an aromatic dicarboxylic acid.

[0190] The polyarylate resin according to the present invention may be a commercially available product, and an example thereof is PAR resin "U-100" manufactured by Unitika Ltd., having a weight average molecular weight (Mw) of 100,000.

[0191] [2.2] Additives The functional layer may further contain other components other than those mentioned above, if necessary. Examples of other components include rubber particles, the above-mentioned matting agent (fine particles), plasticizers, ultraviolet absorbers, etc. Among them, rubber particles and plasticizers can be used as a means for imparting hydrophobicity to the film and controlling the humidity expansion coefficient CHE of the functional layer, so that the curl characteristics of the laminate can be controlled by appropriately adjusting the material and additive amount. In addition, from the viewpoint of imparting toughness (flexibility) to the functional layer, it is preferable to further contain rubber particles.

[0192] <Rubber particles> The rubber particles are particles containing a rubber-like polymer. The rubber-like polymer is a soft crosslinked polymer having a glass transition temperature of 20° C. or less. Examples of such crosslinked polymers include butadiene-based crosslinked polymers, (meth)acrylic crosslinked polymers, and organosiloxane crosslinked polymers. Among them, (meth)acrylic crosslinked polymers are preferred, and acrylic crosslinked polymers (acrylic rubber-like polymers) are more preferred, from the viewpoint of a small difference in refractive index from the (meth)acrylic resin and less loss of transparency of the functional layer.

[0193] That is, the rubber particles are preferably particles containing the acrylic rubber-like polymer (a).

[0194] Regarding the acrylic rubber polymer (a): The acrylic rubber-like polymer (a) is a crosslinked polymer containing a structural unit derived from an acrylic acid ester as a main component. "Containing as a main component" means that the content of the structural unit derived from an acrylic acid ester is within the range described below. The acrylic rubber-like polymer (a) is preferably a crosslinked polymer containing a structural unit derived from an acrylic acid ester, a structural unit derived from another monomer copolymerizable therewith, and a structural unit derived from a polyfunctional monomer having two or more radically polymerizable groups (non-conjugated reactive double bonds) in one molecule.

[0195] The acrylic acid ester is preferably an alkyl acrylate ester having an alkyl group having 1 to 12 carbon atoms, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, benzyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, etc. The acrylic acid ester may be one type or two or more types.

[0196] The content of the structural units derived from the acrylic acid ester is preferably 40 to 80 mass %, more preferably 50 to 80 mass %, based on the total structural units constituting the acrylic rubber-like polymer (a1). When the content of the acrylic acid ester is within the above range, it is easy to impart sufficient toughness to the protective film. The copolymerizable other monomer is a monomer copolymerizable with an acrylic acid ester other than a polyfunctional monomer. That is, the copolymerizable monomer does not have two or more radical polymerizable groups. Examples of the copolymerizable monomer include methacrylic acid esters such as methyl methacrylate; styrenes such as styrene and methylstyrene; (meth)acrylonitriles; (meth)acrylamides; and (meth)acrylic acid. Among them, the copolymerizable other monomer preferably includes styrenes. The copolymerizable other monomer may be one type or two or more types.

[0197] The content of structural units derived from other copolymerizable monomers is preferably from 5 to 55 mass %, and more preferably from 10 to 45 mass %, based on all structural units constituting the acrylic rubber-like polymer (a).

[0198] Examples of the polyfunctional monomer include allyl (meth)acrylate, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, diallyl maleate, divinyl adipate, divinyl benzene, ethylene glycol di(meth)acrylate, diethylene glycol (meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate.

[0199] The content of the structural unit derived from the polyfunctional monomer is preferably 0.05 to 10 mass % and more preferably 0.1 to 5 mass % based on the total structural units constituting the acrylic rubber-like polymer (a). When the content of the polyfunctional monomer is 0.05 mass % or more, the degree of crosslinking of the obtained acrylic rubber-like polymer (a) is easily increased, so that the hardness and rigidity of the obtained functional layer are not excessively impaired, and when it is 10 mass % or less, the toughness of the functional layer is not easily impaired.

[0200] The monomer composition constituting the acrylic rubber-like polymer (a) can be measured, for example, by the peak area ratio detected by pyrolysis GC-MS.

[0201] The glass transition temperature (Tg) of the rubbery polymer is preferably 0° C. or lower, and more preferably −10° C. or lower. When the glass transition temperature (Tg) of the rubbery polymer is 0° C. or lower, it is possible to impart appropriate toughness to the film. The glass transition temperature (Tg) of the rubbery polymer is measured by the same method as described above.

[0202] The glass transition temperature (Tg) of the rubber-like polymer can be adjusted by the composition of the rubber-like polymer. For example, in order to lower the glass transition temperature (Tg) of the acrylic rubber-like polymer (a), it is preferable to increase the mass ratio of the acrylic acid ester having an alkyl group with 4 or more carbon atoms to the other copolymerizable monomer in the acrylic rubber-like polymer (a) (for example, 3 or more, preferably 4 to 10).

[0203] The particles containing the acrylic rubber-like polymer (a) may be particles made of the acrylic rubber-like polymer (a), or particles having a hard layer made of a hard crosslinked polymer (c) having a glass transition temperature of 20° C. or higher and a soft layer made of the acrylic rubber-like polymer (a) arranged around the hard layer (these are also called "elastomers"); or particles made of an acrylic graft copolymer obtained by polymerizing a mixture of monomers such as methacrylic acid esters in at least one stage in the presence of the acrylic rubber-like polymer (a). The particles made of the acrylic graft copolymer may be core-shell type particles having a core containing the acrylic rubber-like polymer (a) and a shell covering the core.

[0204] Core-shell type rubber particles containing acrylic rubber-like polymers: (Core) The core part contains an acrylic rubber-like polymer (a) and may further contain a hard crosslinked polymer (c) as necessary. That is, the core part may have a soft layer made of an acrylic rubber-like polymer and a hard layer made of a hard crosslinked polymer (c) disposed inside the soft layer.

[0205] The crosslinked polymer (c) may be a crosslinked polymer mainly composed of a methacrylic acid ester. That is, the crosslinked polymer (c) is preferably a crosslinked polymer containing a structural unit derived from a methacrylic acid alkyl ester, a structural unit derived from another monomer copolymerizable therewith, and a structural unit derived from a polyfunctional monomer.

[0206] The methacrylic acid alkyl ester may be the above-mentioned methacrylic acid alkyl ester; the other copolymerizable monomer may be the above-mentioned styrenes, acrylic acid esters, etc.; and the polyfunctional monomer may be the same as those exemplified as the above-mentioned polyfunctional monomers.

[0207] The content of the structural unit derived from the methacrylic acid alkyl ester may be 40 to 100% by mass based on all structural units constituting the crosslinked polymer (c). The content of the structural unit derived from the other copolymerizable monomer may be 60 to 0% by mass based on all structural units constituting the other crosslinked polymer (c). The content of the structural unit derived from the polyfunctional monomer may be 0.01 to 10% by mass based on all structural units constituting the other crosslinked polymer.

[0208] (Shell part) The shell portion contains a methacrylic polymer (b) (another polymer) that is graft-bonded to the acrylic rubber-like polymer (a) and contains, as a main component, a structural unit derived from a methacrylic acid ester. "Containing as a main component" means that the content of the structural unit derived from a methacrylic acid ester falls within the range described below.

[0209] The methacrylic acid ester constituting the methacrylic polymer (b) is preferably a methacrylic acid alkyl ester, such as methyl methacrylate, in which the alkyl group has a carbon number of 1 to 12. The methacrylic acid ester may be one type or two or more types.

[0210] The content of the methacrylic acid ester is preferably 50% by mass or more based on all structural units constituting the methacrylic polymer (b). When the content of the methacrylic acid ester is 50% by mass or more, compatibility with the methacrylic resin containing a structural unit derived from methyl methacrylate as a main component is easily obtained. From the above viewpoint, the content of the methacrylic acid ester is more preferably 70% by mass or more based on all structural units constituting the methacrylic polymer (b).

[0211] The methacrylic polymer (b) may further contain structural units derived from other monomers copolymerizable with the methacrylic acid ester. Examples of the copolymerizable other monomers include acrylic acid esters such as methyl acrylate, ethyl acrylate, and n-butyl acrylate; and (meth)acrylic monomers having an alicyclic ring, a heterocyclic ring, or an aromatic ring (ring-containing (meth)acrylic monomers) such as benzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and phenoxyethyl (meth)acrylate.

[0212] The content of structural units derived from copolymerizable monomers is preferably 50% by mass or less, and more preferably 30% by mass or less, based on all structural units constituting the methacrylic polymer (b).

[0213] In the present embodiment, since the functional layer is not stretched, the shape of the rubber particles can be close to a perfect sphere. That is, when observing the cross section or surface of the functional layer, the aspect ratio of the rubber particles can be about 1 to 2.

[0214] The average particle size of the rubber particles is preferably 100 to 400 nm. When the average particle size of the rubber particles is 100 nm or more, sufficient toughness and stress relaxation properties are easily imparted to the functional layer, and when it is 400 nm or less, the transparency of the functional layer is less likely to be impaired. From the same viewpoint, the average particle size of the rubber particles is more preferably 150 to 300 nm.

[0215] The average particle size of the rubber particles can be calculated by the following method.

[0216] The average particle size of rubber particles can be measured as the average of the circle-equivalent diameters of 100 particles obtained by SEM or TEM photography of the surface or slice of the laminated film. The circle-equivalent diameter can be obtained by converting the projected area of ​​the particle obtained by photography into the diameter of a circle having the same area. In this case, rubber particles observed by SEM observation and / or TEM observation at a magnification of 5000 times are used to calculate the average particle size.

[0217] The content of the rubber particles is not particularly limited, but is preferably 5 to 40% by mass, and more preferably 7 to 30% by mass, based on the functional layer.

[0218] [2.3] Physical Properties <Coefficient of humidity expansion at 23℃ (CHE2)> The humidity expansion coefficient (CHE2) of the functional layer at 23°C is preferably in the range of 1 to 30 ppm / % RH from the viewpoint of controlling the direction and degree of curling in relation to the preferred humidity expansion coefficient (CHE1) of the base film. If the humidity expansion coefficient CHE2 of the transparent functional layer is 1 ppm or more, the effect of facilitating the peeling process after lamination is exhibited, and if it is 30 ppm or less, the effect of suppressing the occurrence of errors and unevenness during lamination is exhibited. It is more preferably in the range of 3 to 20 ppm / % RH, and even more preferably in the range of 5 to 15 ppm / % RH.

[0219] Phase difference Ro and Rt The functional layer according to the present invention can function as an optical film such as a retardation film by being attached to a polarizer after being peeled off from the substrate film. From the viewpoint of using the functional layer as a retardation film for IPS mode, for example, the in-plane retardation Ro measured at a measurement wavelength of 590 nm under an environment of 23° C. and 55% RH is preferably 0 to 10 nm, more preferably 0 to 5 nm, and the thickness direction retardation Rt of the functional layer is preferably −40 to 40 nm, more preferably −25 to 25 nm.

[0220] Ro and Rt are defined by the following formulas, respectively.

[0221] Formula (a): Ro = (n x -n y )×d Formula (b): Rt = ((n x +n y ) / 2-n z )×d (In the formula, n xrepresents the refractive index in the in-plane slow axis direction (the direction in which the refractive index is maximum) of the functional layer, n y represents the refractive index in a direction perpendicular to the in-plane slow axis of the functional layer, n z represents the refractive index in the thickness direction of the functional layer, d represents the thickness of the functional layer (nm). The in-plane slow axis of the functional layer can be confirmed by an automatic birefringence meter Axoscan (Axo Scan Mueller Matrix Polarimeter, manufactured by Axometrics).

[0222] Ro and Rt can be measured by the following method.

[0223] 1) The functional layer is conditioned for 24 hours in an environment of 23°C and 55% RH. The average refractive index of this film is measured with an Abbe refractometer, and the thickness d is measured with a commercially available micrometer.

[0224] 2) After humidity conditioning, the retardation Ro and Rt of the film at a measurement wavelength of 590 nm are measured in an environment of 23° C. and 55% RH using an automatic birefringence meter Axoscan (Axo Scan Mueller Matrix Polarimeter, manufactured by Axometrics).

[0225] The retardation Ro and Rt of the functional layer can be adjusted by, for example, the type of resin, the stretching conditions, the drying conditions, etc. For example, Rt can be reduced by increasing the drying temperature.

[0226] [3] Manufacturing method of laminated film The shape of the laminated film of the present invention is not particularly limited, and may be, for example, a strip shape. That is, the laminated film of the present invention is preferably wound into a roll in a direction perpendicular to its width direction to form a roll body.

[0227] [3.1] Manufacturing method of laminated film [Manufacturing method] The method for manufacturing a laminated film of the present invention includes the steps of 1) obtaining a solution for a functional layer, 2) applying the obtained functional layer solution to the surface of a base film, and 3) removing the solvent from the applied solution for a functional layer to form a functional layer.

[0228] 1) Step of obtaining a solution for the functional layer A solution for forming a functional layer containing the above-mentioned resin and a solvent is prepared.

[0229] The solvent used in the functional layer solution is not particularly limited as long as it can disperse or dissolve the resin well.For example, the organic solvent used in the present invention includes alcohols (methanol, ethanol, diol, triol, tetrafluoropropanol, etc.), glycols, cellosolves, ketones (acetone, methyl ethyl ketone, etc.), carboxylic acids (formic acid, acetic acid, etc.), carbonates (ethylene carbonate, propylene carbonate, etc.), esters (ethyl acetate, propyl acetate, etc.), ethers (isopropyl ether, THF, etc.), amides (dimethyl sulfoxide, etc.), hydrocarbons (heptane, etc.), nitriles (acetonitrile, etc.), aromatics (cyclohexylbenzene, toluene, xylene, chlorobenzene, etc.), alkyl halides (dichloromethane (also called "methylene chloride"), etc.), amines (1,4-diazabicyclo[2.2.2]octane, diazabicycloundecene, etc.), lactones, etc.

[0230] Among them, the solvent for the functional layer is preferably a chlorine-based solvent having a boiling point of 100° C. or less under atmospheric pressure, more specifically, dichloromethane (also called "methylene chloride"), from the viewpoint of ease of handling and controlling the humidity expansion coefficient when preparing a dope for the functional layer and forming a film. This is preferable from the viewpoint of high solubility and fast drying speed, thereby adjusting the film quality of the coating film and thus controlling the humidity expansion coefficient when preparing a dope for the functional layer and forming a film. In addition, the humidity expansion coefficient can be controlled by adding a hydrophilic solvent. Examples of hydrophilic solvents include ketones and alcohols, and alcohols are preferable. More preferable are isopropanol, ethanol, methanol, etc., and most preferable is methanol. The amount added is preferably in the range of 1 to 20% by mass, and more preferably in the range of 3 to 10% by mass.

[0231] From the viewpoint of easily adjusting the viscosity to the range described below, the resin concentration of the solution for the functional layer is preferably, for example, 1.0 to 20 mass %. Furthermore, from the viewpoint of reducing the amount of shrinkage of the coating film when it is dried, the resin concentration of the solution for the functional layer is preferably moderately high, more preferably more than 5 mass % to 20 mass % or less, and even more preferably more than 5 mass % to 15 mass % or less. Furthermore, by adjusting the solution concentration, the time until the film is formed is shortened, and the drying time can also be a means of controlling the CHE of the functional layer. To increase the concentration, a mixed solvent may be used as appropriate.

[0232] The viscosity of the solution for the functional layer is not particularly limited as long as it is sufficient to form a functional layer of the desired thickness, but is preferably, for example, 5 to 5000 mPa·s. When the viscosity of the solution for the functional layer is 5 cP or more, a functional layer of appropriate thickness is easily formed, and when it is 5000 mPa·s or less, the occurrence of thickness unevenness due to an increase in the viscosity of the solution can be suppressed. From the same viewpoint, the viscosity of the solution for the functional layer is more preferably 100 to 1000 mPa·s. The viscosity of the solution for the functional layer can be measured at 25°C using an E-type viscometer.

[0233] 2) A step of applying a solution for the functional layer Next, the obtained solution for forming a functional layer is applied to the surface of the base film. Specifically, the obtained solution for forming a functional layer is applied to the surface of the base film.

[0234] The method for applying the solution for the functional layer is not particularly limited and may be a known method such as back-roll coating, gravure coating, spin coating, wire bar coating, roll coating, etc. Among these, the back-coating method is preferred from the viewpoint of forming a coating film having a thin and uniform thickness.

[0235] 3) Forming the functional layer Next, the solvent is removed from the functional layer solution applied to the substrate film to form a functional layer.

[0236] Specifically, the functional layer solution applied to the base film is dried. The drying can be performed, for example, by blowing air or heating. In particular, from the viewpoint of easily suppressing curling of the laminated film, drying can also be performed by blowing air.

[0237] By adjusting the drying conditions (e.g. drying temperature, drying air volume, drying time, etc.), it is possible to control the density of the functional layer, and thus adjust the CHE. To increase the CHE, it is preferable to adjust the film quality to be coarser; specifically, it is preferable to increase the drying speed, and the drying speed should be 0.001 to 0.05 kg / hr m 2 It is preferable that the maximum flow rate is 0.002 to 0.01 kg / hr m. 2 It is more preferable that:

[0238] The drying rate is expressed as the mass of solvent evaporated per unit time and unit area. The drying rate can usually be adjusted by the drying temperature. The drying temperature depends on the type of solvent used, but can be, for example, 50 to 200°C ((Tb-50) to (Tb+50)°C, where Tb is the boiling point of the solvent used). Temperature control may be performed in multiple stages. After a certain degree of drying has progressed, the drying rate and film quality can be controlled by drying at a higher temperature.

[0239] As described above, the laminate film according to the present embodiment may be in a belt-like shape. Therefore, it is preferable that the method for producing the laminate film according to the present embodiment further includes a step 4) of winding the belt-like laminate film into a roll to form a roll body.

[0240] 4) A process of winding up the laminated film to obtain a roll body. The obtained strip-shaped laminate film is wound up in a direction perpendicular to its width direction into a roll to form a roll body.

[0241] The length of the strip-shaped laminated film is not particularly limited, but may be, for example, about 100 to 10,000 m. The width of the strip-shaped laminated film is preferably 1 m or more, more preferably 1.3 to 4 m. From the viewpoint of improving the uniformity of the film, it is more preferably 1.6 to 2.5 m.

[0242] [Manufacturing equipment] The method for producing the laminated film of the present invention can be carried out, for example, by using a production apparatus shown in FIG.

[0243] 3 is a schematic diagram of a manufacturing apparatus B200 for carrying out the laminated film manufacturing method according to this embodiment. The manufacturing apparatus B200 has a supply section B210, a coating section B220, a drying section B230, a cooling section B240, and a winding section B250. Ba to Bd denote transport rolls that transport the base film B110.

[0244] The supply section B210 has a payout device (not shown) that pays out a roll B201 of the strip-shaped base film B110 wound around a core.

[0245] The coating section B220 is a coating device that includes a backup roll B221 that holds the base film B110, a coating head B222 that applies a functional layer solution to the base film B110 held by the backup roll B221, and a reduced pressure chamber B223 provided upstream of the coating head B222.

[0246] The flow rate of the functional layer solution discharged from the coating head B222 can be adjusted by a pump (not shown). The flow rate of the functional layer solution discharged from the coating head B222 is set to an amount that can stably form a coating layer of a predetermined thickness when continuously coated under the previously adjusted conditions of the coating head B222.

[0247] The decompression chamber B223 is a mechanism for stabilizing a bead (a pool of coating liquid) formed between the functional layer solution from the coating head B222 and the base film B110 during coating, and the degree of decompression is adjustable. The decompression chamber B223 is connected to a decompression blower (not shown) so that the inside can be decompressed. The decompression chamber B223 is in a state where there is no air leakage, and the gap with the backup roll is adjusted to be narrow so that a stable bead of coating liquid can be formed.

[0248] The drying section B230 is a drying device that dries the coating applied to the surface of the base film B110, and has a drying chamber B231, an inlet B232 for drying gas, and an outlet B233. The temperature and volume of the drying air are appropriately determined depending on the type of coating and the type of base film B110. By setting conditions such as the temperature and volume of the drying air and the drying time in the drying section B230, the amount of residual solvent in the coating after drying can be adjusted. The amount of residual solvent in the coating after drying can be measured by comparing the unit mass of the coating after drying with the mass of the coating after it has been thoroughly dried.

[0249] (Residual Solvent Amount) Since the functional layer is obtained by applying a solution for the functional layer, the solvent derived from the solution may remain. The amount of residual solvent can also be used to control the humidity expansion coefficient, and can be controlled by the concentration of the solvent and coating solution used, the wind speed used to dry the functional layer, the drying temperature and time, the conditions of the drying room (outside air or internal air circulation), the heating temperature of the back roll during application, etc.

[0250] As mentioned above, when the drying speed is high, the membrane becomes sparse and moisture permeates faster, so the humidity expansion coefficient CHE2 increases.

[0251] From the viewpoint of curl balance of the laminate film, it is preferable that the residual solvent amount in the functional layer satisfies the following formula (2), where the residual solvent amount in the base film is S1 and the residual solvent amount in the functional layer is S2. Formula (2) 10 <S1<S2<1000(ppm) Specifically, the residual solvent content of the functional layer is preferably less than 1000 ppm, more preferably less than 800 ppm, and more preferably less than 500 to 700 ppm, taking into consideration the curl balance of the laminated film. In addition, by selecting a solvent / coating process that leaves the solvent in the base film, the adhesion between the laminates is improved. The residual solvent content of the base film is preferably in the range of 10 to 100 ppm.

[0252] The residual solvent amount in the functional layer and the base film can be measured by headspace gas chromatography. In the headspace gas chromatography method, a sample is sealed in a container, heated, and the gas in the container is quickly injected into a gas chromatograph in a state where the container is filled with volatile components, and mass analysis is performed to identify the compounds and quantify the volatile components. In the headspace method, the gas chromatograph makes it possible to observe all peaks of the volatile components, and by using an analysis method that utilizes electromagnetic interaction, it is also possible to quantify volatile substances, monomers, etc. with high accuracy.

[0253] The cooling section B240 cools the temperature of the base film B110 having the coating film (functional layer B120) obtained by drying in the drying section B230, and adjusts it to an appropriate temperature. The cooling section B240 has a cooling chamber B241, a cooling air inlet B242, and a cooling air outlet B243. The temperature and volume of the cooling air can be determined appropriately depending on the type of coating film and the type of base film B110. Furthermore, if an appropriate cooling temperature can be achieved without providing the cooling section B240, the cooling section B240 may not be necessary.

[0254] The winding section B250 is a winding device (not shown) for winding up the base film B110 on which the transparent functional layer B120 is formed, to obtain a roll body B251. (Thickness) The thickness d2 of the functional layer is usually thinner than the thickness d1 of the base film. Specifically, from the viewpoint of thinning the polarizing plate, the thickness d2 of the functional layer is preferably in the range of 1 to 19 μm, and more preferably in the range of 2 to 10 μm.

[0255] [4] Polarizing plate The polarizing plate has a polarizer and a laminate film or a functional layer disposed on at least one surface of the polarizer. The polarizer and the laminate film or the functional layer are preferably bonded to each other via an adhesive layer.

[0256] 4A and 4B show an example of the layer structure of the polarizing plate of the present invention, but the present invention is not limited thereto.

[0257] FIG. 4A is a cross-sectional view of a polarizing plate with a substrate film.

[0258] A polarizing plate 10a is fabricated by bonding the functional layer 3 side of the laminated film 1 of the present invention (substrate film 2 and functional layer 3) to a polarizer 5 via an adhesive layer 4. If necessary, an opposing film 6 may be bonded via the adhesive layer 4 to the surface of the polarizer 5 opposite to the surface to which the laminated film 1 of the present invention is bonded.

[0259] When the polarizing plate 10a is provided in, for example, a display device (not shown), the laminate film 1 of the present invention may be attached to the display element side via an adhesive layer (not shown), or the counter film 6 may be attached to the display element side via an adhesive layer (not shown). When the laminate film 1 of the present invention is attached, the embodiment shown in the following Figure 4(b) in which the base film 2 is peeled off from the laminate film 1 is preferable.

[0260] FIG. 4B is a cross-sectional view of the polarizing plate from which the base film has been peeled off.

[0261] The functional layer 3 side of the laminated film 1 (base film 2 and functional layer 3) of the present invention is attached to a polarizer 5 via an adhesive layer 4 to process a polarizing plate 10b. During or after processing of the polarizing plate, the base film 2 is peeled off from the functional layer 3 to process a thin polarizing plate 10b. If necessary, an opposing film 6 may be attached via an adhesive layer 4 to the surface of the polarizer 5 opposite to the surface to which the functional layer 3 of the present invention is attached.

[0262] When the polarizing plate 10b is provided in, for example, a display device (not shown), the functional layer 3 according to the present invention may be attached to the display element side via an adhesive layer (not shown), and the opposing film 6 may be attached to the display element side via an adhesive layer (not shown).

[0263] [4.1] Polarizer A polarizer is an element that transmits only light with a certain polarization plane. The polarizer can usually be a polyvinyl alcohol-based polarizing film. Examples of polyvinyl alcohol-based polarizing films include polyvinyl alcohol-based films dyed with iodine and dichroic dyes.

[0264] The polyvinyl alcohol polarizing film may be a film obtained by uniaxially stretching a polyvinyl alcohol film and then dyeing it with iodine or a dichroic dye (preferably further subjecting it to a durability treatment with a boron compound); or a film obtained by uniaxially stretching a polyvinyl alcohol film and then dyeing it with iodine or a dichroic dye (preferably further subjecting it to a durability treatment with a boron compound). The absorption axis of the polarizer is usually parallel to the maximum stretching direction.

[0265] The thickness of the polarizer is preferably from 5 to 30 μm, and from the viewpoint of making the polarizing plate thinner, it is more preferably from 5 to 20 μm.

[0266] [4.2] Laminated film or functional layer, and opposing film A base film or a functional layer constituting the laminated film of the present invention is disposed on at least one surface of the polarizer. Either of the base film or the functional layer constituting the laminated film can function as a polarizer protective film. In the present embodiment, it is preferable that a functional layer is disposed on one surface of the polarizer, and another protective film is disposed on the other surface.

[0267] Examples of the facing film include a cycloolefin resin, a polypropylene resin, an acrylic resin, a polyester resin, a polyarylate resin, a cellulose ester resin, a styrene resin, or a composite resin thereof. Among them, a resin film containing a cycloolefin resin, an acrylic resin, and a polyester resin is preferable.

[0268] [4.3] Adhesive layer The adhesive layer is disposed between the functional layer and the polarizer, and between the opposing film and the polarizer. The adhesive layer disposed between the functional layer and the polarizer and the adhesive layer disposed between the opposing film and the polarizer may be the same or different.

[0269] The adhesive layer may be a layer of a cured product of an active energy ray-curable adhesive, or may be a layer obtained from a water-soluble polymer.

[0270] The active energy ray-curable adhesive may be a photoradical polymerizable composition or a photocationically polymerizable composition, of which a photocationically polymerizable composition is preferred.

[0271] The photocationically polymerizable composition contains an epoxy compound and a photocationic polymerization initiator.

[0272] In the case of a water-soluble polymer, the adhesive can be applied through an adhesive made of a vinyl alcohol-based polymer, or an adhesive made of at least a water-soluble crosslinking agent of a vinyl alcohol-based polymer, such as boric acid, borax, glutaraldehyde, melamine, or oxalic acid. Such an adhesive layer is formed as a coating and drying layer of an aqueous solution, and other additives and catalysts such as acids can be added as necessary when preparing the aqueous solution. In the case of a process using a water-soluble polymer, the laminate may curl due to the penetration of the water contained therein, which may reduce the yield of the polarizing plate. It is also an object of the present invention to prevent such process errors.

[0273] The thickness of each adhesive layer is not particularly limited, but is preferably 0.01 to 10 μm, and more preferably 0.01 to 5 μm.

[0274] [4.4] Adhesive layer The pressure-sensitive adhesive layer is a layer for attaching the polarizing plate to a display element such as a liquid crystal cell, and may be formed on either side of the polarizing plate, but can be disposed on the side of the functional layer opposite the polarizer.

[0275] The pressure-sensitive adhesive layer is preferably a pressure-sensitive adhesive composition containing a base polymer, a prepolymer and / or a crosslinkable monomer, a crosslinking agent and a solvent, which is dried and partially crosslinked, i.e., at least a part of the pressure-sensitive adhesive composition is crosslinked.

[0276] Examples of the pressure-sensitive adhesive composition include an acrylic pressure-sensitive adhesive composition having a (meth)acrylic polymer as a base polymer, a silicone pressure-sensitive adhesive composition having a silicone polymer as a base polymer, and a rubber pressure-sensitive adhesive composition having a rubber as a base polymer. Among them, from the viewpoints of transparency, weather resistance, heat resistance, and processability, an acrylic pressure-sensitive adhesive composition is preferred.

[0277] The pressure-sensitive adhesive composition may further contain various additives, such as a tackifier, a plasticizer, glass fibers, glass beads, metal powder, other fillers, pigments, colorants, fillers, antioxidants, ultraviolet absorbers, and silane coupling agents, as necessary.

[0278] The thickness of the pressure-sensitive adhesive layer is usually about 3 to 100 μm, and preferably 5 to 50 μm.

[0279] The surface of the pressure-sensitive adhesive layer is protected by a release film that has been subjected to a release treatment. Examples of the release film include plastic films such as acrylic films, polycarbonate films, polyester films, and fluororesin films.

[0280] [4.4] Manufacturing method of polarizing plate The polarizing plate according to the present embodiment can be manufactured by laminating the laminated film to at least one surface of a polarizer and peeling off the base film. The laminated film may be laminated to only one surface of the polarizer or to both surfaces of the polarizer. From the viewpoint of transmittance, it is preferable to laminate the laminated film to one surface of the polarizer and to laminate an opposing film, which is another protective film, to the other surface of the polarizer.

[0281] The substrate film side or the functional layer side of the laminate film of the present invention may be attached to the polarizer. It is preferable to attach the functional layer side and use the substrate film as a protective film, or to peel it off and use only the thin functional layer.

[0282] Therefore, when manufacturing a polarizing plate roll by winding up a laminate film while laminating it to at least one surface of a polarizer, a preferred manufacturing method for a polarizing plate roll includes a step of laminating the laminate film to the polarizer while winding it up so that the layers are polarizer, functional layer, and base film from the inside of the roll. Also, a preferred embodiment is a method of peeling off the base film in the laminate film before laminating the laminate film to the polarizer, drying, and winding it up.

[0283] Basically, the polarizing plate of the present invention can be manufactured through the steps of 1) bonding a functional layer of the above-mentioned laminate film to one side of a polarizer (the base film arranged on the side of the functional layer opposite the polarizer may be left attached or may be peeled off as necessary), and 2) bonding an opposing film, which is another protective film, to the other side of the polarizer.

[0284] 1) Functional layer lamination process The functional layer of the laminated film is attached to one surface of the polarizer via an adhesive. The surface of the functional layer to be attached or one surface of the polarizer may be subjected to a pretreatment such as a corona treatment as necessary.

[0285] For example, when a water-soluble polymer adhesive is used as the adhesive, 1) a surface treatment such as corona treatment is applied to the surface of the functional layer of the laminated film as necessary. Then, the functional layer of the laminated film is laminated on one side of the polarizer via the water-soluble polymer adhesive. 2) Then, an opposing film, which is another protective film, is attached to the other side of the polarizer. Specifically, a surface treatment such as corona treatment is applied to the surface of the opposing film as necessary. Then, the opposing film is laminated on the other side of the polarizer via the water-soluble polymer adhesive, and then a drying process is performed stepwise in a temperature range of, for example, 50 to 80°C.

[0286] Steps 1) and 2) may be carried out simultaneously or sequentially. From the viewpoint of increasing production efficiency, steps 1) and 2) are preferably carried out simultaneously.

[0287] The polarizing plate according to the present embodiment may be in a strip shape. Therefore, in steps 1) and 2), the polarizing plate is preferably processed by unwinding the functional layer of the strip-shaped laminate film, the strip-shaped polarizer, and the strip-shaped other protective film (opposite film) from rolls and laminating them together in a roll-to-roll manner.

[0288] It is also preferable to further carry out a step of winding the strip-shaped polarizing plate into a roll to form a roll body. In this step, the length and width of the strip-shaped polarizing plate are the same as those of the strip-shaped laminate film in step 4) of the laminate film manufacturing method.

[0289] In the method for producing a polarizing plate roll of the present invention, in the step of winding up the laminate film 1 while bonding it to at least one surface of a polarizer 5, it is also preferable to form a polarizing plate roll by a step of winding up the laminate film 1 while bonding it to the polarizer 5 in the layer order of polarizer 5, adhesive layer 4, functional layer 3, and base film 2 from the inside of the roll. In this case, since the base film 2 according to the present invention is disposed on the outside of the polarizing plate roll, it exhibits a function as a protective film, prevents the functional layer 2 from being scratched during processing of the polarizing plate, suppresses curling, and facilitates handling.

[0290] At this time, if necessary, an opposing film 6 may be attached to the surface opposite to the surface to which the laminate film 1 is attached via an adhesive layer 4 while being wound up to form a polarizing plate roll.

[0291] [5] Display device The display device according to the present embodiment has a display element such as a liquid crystal cell or an organic electroluminescence (also referred to as "EL") element, and a polarizing plate manufactured by the above manufacturing method. In particular, the display device according to the present embodiment is preferably a liquid crystal display device having a liquid crystal cell and a polarizing plate manufactured by the above manufacturing method.

[0292] That is, the liquid crystal display device includes a liquid crystal cell, a first polarizing plate arranged on one surface of the liquid crystal cell, and a second polarizing plate arranged on the other surface of the liquid crystal cell. At least one of the first polarizing plate and the second polarizing plate is a polarizing plate according to the present embodiment. It is preferable that the absorption axis of the first polarizer in the first polarizing plate and the absorption axis of the second polarizing plate are perpendicular to each other (in a crossed Nicol configuration).

[0293] The display mode of the liquid crystal cell can be, for example, STN (Super-Twisted Nematic), TN (Twisted Nematic), OCB (Optically Compensated Bend), HAN (Hybrid-aligned Nematic), VA (Vertical Alignment, MVA (Multi-domain Vertical Alignment), PVA (Patterned Vertical Alignment), IPS (In-Plane-Switching), etc. For example, the IPS mode is preferable for liquid crystal display devices for mobile devices. EXAMPLES

[0294] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.

[0295] Example 1 [1] Laminated film material [1-1] Base film <Base film A> Polyethylene terephthalate film (PET film): (Toyobo TN100, with release layer containing non-silicone release agent, thickness 38 μm)

[0296] <Base film B> Polyethylene terephthalate film (PET film) (Toyobo TN100) stretched 13% in the TD direction (thickness 30 μm) <Base film C> Polyethylene terephthalate film (PET film) (Toyobo TN100) stretched 30% in the TD direction (thickness 25 μm)

[0297] <Base film D> Polyethylene terephthalate film (PET film) (Toyobo TN100) heat-relaxed at 150°C for 30 seconds (thickness 38μm) <Base film E> Triacetyl cellulose film (TAC) (Konica Minolta KC4UA, no release layer, thickness 38 μm) <Base film F> Cycloolefin film (COP) (JSR ARTON G7810, no release layer, thickness 38 μm) <Base film G> High density polyethylene (HDPE) (Hi-Zex 2200J (Prime Polymer), thickness 38 μm)

[0298] The humidity expansion coefficient CHE1 at 23° C. of each of the base films A to G was measured by the following method.

[0299] (Humidity expansion coefficient CHE1 at 23°C) The humidity expansion coefficient CHE1 at 23° C. of the substrate film was measured with reference to JIS K7197. A film sample was fixed in a thermo-hygrostat so that it was 1 cm wide and 15 cm long, and dehumidified until it reached a constant humidity (approximately 30% RH). After the film length reached a constant level, it was re-humidified (approximately 80% RH) and began to elongate due to moisture absorption. After approximately 24 hours, the moisture absorption reached equilibrium and the film also elongated. The amount of elongation at this time was calculated using the following formula. During this time, the ambient temperature was kept constant at 23°C. Humidity expansion coefficient at 23°C (ppm / %RH) = expansion amount (cm) / (sample length (cm) x humidity difference) x 10 6

[0300] [1-2] Solution for functional layer (1) Preparation of materials <Resin> 1. COP (G7810): ARTON G7810 manufactured by JSR Corporation, Mw: 140,000, cycloolefin resin with carboxylic acid group 2. Fumaric acid resin: Tosoh fumaric acid diester resin, number average molecular weight 120,000 3. Acrylic: MMA / PMI / MADA copolymer (60 / 20 / 20 mass ratio), Mw: 1.5 million, Tg: 137°C (abbreviations are as follows: MMA: methyl methacrylate, PMI: phenylmaleimide, and MADA: adamantyl acrylate) 4. Polyarylate: Unitika U-100 5. COP (ZNX330R): ZNX330R manufactured by Zeon Corporation 6. A-DCP: Tricyclodecane dimethanol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) 7. PSt / polyarylate (mass ratio 5:5) mixture: Pst (polystyrene: manufactured by PS Japan Co., Ltd., Mw: 500,000: manufactured by PS Japan Co., Ltd.), polyarylate (compound P below) 8. PSt: Polystyrene (Mw: 500,000: PS Japan) 9. TAC: Acetyl cellulose with an acetyl substitution degree of 2.9

[0301] [ka]

[0302] The glass transition temperature (Tg) and weight average molecular weight (Mw) of Resins 1 to 9 were measured by the following method.

[0303] (glass transition temperature) The glass transition temperature (Tg) of the resin was measured using DSC (Differential Scanning Colorimetry) in accordance with JIS K 7121-2012.

[0304] (Weight average molecular weight) The weight average molecular weight (Mw) of the resin was measured using gel permeation chromatography (HLC8220GPC manufactured by Tosoh Corporation) and a column (TSK-GEL G6000HXL-G5000HXL-G5000HXL-G4000HXL-G3000HXL in series manufactured by Tosoh Corporation). 20 mg ± 0.5 mg of the sample was dissolved in 10 ml of tetrahydrofuran and filtered through a 0.45 mm filter. 100 ml of this solution was injected into the column (temperature 40°C), and the measurement was performed with a detector RI temperature of 40°C, and the value converted into styrene was used.

[0305] <Rubber particles R1> Rubber particles R1 prepared by the following method were used.

[0306] The following materials were charged into an 8 L polymerization apparatus equipped with a stirrer.

[0307] Deionized water 180 parts by weight Polyoxyethylene lauryl ether phosphate 0.002 parts by mass Boric acid 0.4725 parts by mass Sodium carbonate 0.04725 parts by mass Sodium hydroxide 0.0076 parts by mass

[0308] After the inside of the polymerization machine was fully replaced with nitrogen gas, the inside temperature was set to 80°C, and 0.021 parts by mass of potassium persulfate was added as a 2% aqueous solution. Next, a mixture of 21 parts by mass of a monomer mixture (c') consisting of 84.6% by mass of methyl methacrylate, 5.9% by mass of butyl acrylate, 7.9% by mass of styrene, 0.5% by mass of allyl methacrylate, and 1.1% by mass of n-octyl mercaptan and 0.07 parts by mass of polyoxyethylene lauryl ether phosphoric acid was added continuously to the above solution over a period of 63 minutes. The polymerization reaction was continued for another 60 minutes to obtain an innermost hard polymer (c).

[0309] Then, 0.021 parts by mass of sodium hydroxide was added as a 2% by mass aqueous solution, and 0.062 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution. Next, a mixed solution of 0.25 parts by mass of polyoxyethylene lauryl ether phosphoric acid and 39 parts by mass of a monomer mixture (a') consisting of 80.0% by mass of butyl acrylate, 18.5% by mass of styrene, and 1.5% by mass of allyl methacrylate was added continuously over 117 minutes. After the addition was completed, 0.012 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution, and the polymerization reaction was continued for 120 minutes to obtain a soft layer (a layer consisting of an acrylic rubber-like polymer (a)). The glass transition temperature (Tg) of the soft layer was -30°C. The glass transition temperature of the soft layer was calculated by averaging the glass transition temperatures of the homopolymers of each monomer constituting the acrylic rubber-like polymer (a) according to the composition ratio.

[0310] Then, 0.04 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution, and 26.1 parts by mass of a monomer mixture (b') consisting of 97.5% by mass of methyl methacrylate and 2.5% by mass of butyl acrylate was continuously added over 78 minutes. The polymerization reaction was continued for another 30 minutes to obtain a polymer (b).

[0311] The obtained polymer was poured into a 3% by mass aqueous solution of sodium sulfate for salting out and coagulation. After repeated dehydration and washing, it was dried to obtain acrylic graft copolymer particles (rubber particles R1) with a three-layer structure. The average particle size of the obtained rubber particles R1 was 200 nm.

[0312] The average particle size of the rubber particles was measured by the following method.

[0313] (Average particle size) The particle size of the rubber particles in the resulting dispersion was measured using a zeta potential / particle size measurement system (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.).

[0314] (2) Preparation of functional layer solution <Preparation of functional layer solution for laminated film 201> The following components were mixed to obtain a functional layer solution 201.

[0315] Toluene (boiling point 110°C): 900 parts by mass COP(G7810): 100 parts by mass

[0316] <Preparation of functional layer solutions for laminated films 202 to 205> Functional layer solutions for laminate films 202 to 205 were obtained in the same manner as for the functional layer solution for laminate film 201, except that the solvents shown in Table I were changed to cyclopentanone (boiling point 131°C) and dichloromethane (methylene chloride, boiling point 41°C).

[0317] <Preparation of functional layer solution for laminated films 206 to 215> The following components were mixed to obtain functional layer solutions 206 to 215. Methylene chloride (boiling point 41°C): 760 parts by mass Methanol (boiling point 65°C): 40 parts by mass COP(G7810): 200 parts by mass

[0318] <Preparation of functional layer solutions for laminated films 216 to 222> The following components were mixed to obtain a functional layer solution 216. Methyl ethyl ketone (MEK: boiling point 80°C) 900 parts by mass Fumaric acid diester resin (written as fumaric acid resin): 100 parts by mass

[0319] The functional layer solutions for laminate films 217-222 were prepared in the same manner as the functional layer solution for laminate film 216, except that the solvent was changed appropriately to a mixture of MEK (boiling point 80°C):toluene (boiling point 110°C) = 7:3 (mass ratio), methylene chloride (boiling point 41°C), and resin concentration (10% by mass or 20% by mass), as shown in Table II.

[0320] <Preparation of functional layer solution for laminated film 223> The following components were mixed to obtain a functional layer solution 223. Methyl ethyl ketone (MEK: boiling point 80°C) 900 parts by mass Acrylic: 100 parts by weight

[0321] <Preparation of functional layer solution for laminated film 224> The following components were mixed to obtain a functional layer solution 224. Methyl ethyl ketone (MEK: boiling point 80°C) 900 parts by mass Acrylic: 80 parts by weight Rubber particles R1: 20 parts by mass

[0322] <Preparation of functional layer solution for laminated film 225> The following components were mixed to obtain functional layer solution 225. Methylene chloride (boiling point 41°C) 900 parts by mass Acrylic: 100 parts by weight

[0323] <Preparation of functional layer solutions for laminated films 226 and 227> The following components were mixed to obtain a functional layer solution 226. Methylene chloride (boiling point 41°C) 800 parts by mass Acrylic: 80 parts by weight Rubber particles R1: 20 parts by mass The following components were mixed to obtain functional layer solution 227. Methylene chloride (boiling point 41°C) 800 parts by mass Acrylic: 160 parts by weight Rubber particles R1: 20 parts by mass

[0324] <Preparation of functional layer solutions for laminated films 228 and 229> The following components were mixed to obtain functional layer solution 228. Toluene (boiling point 110°C): 900 parts by mass Polyarylate (Unitika U-100): 100 parts by mass The functional layer solution for laminate film 229 was prepared in the same manner as the functional layer solution for laminate film 228, except that methylene chloride (boiling point 41°C) was used as the solvent, as shown in Table III.

[0325] <Preparation of functional layer solution for laminated film 230> With reference to Example 1 of JP 2020-3823 A, the following components were mixed to obtain a functional layer solution 230. Cyclohexane (boiling point 81°C): 900 parts by mass COP(ZNX330R) 100 parts by mass

[0326] <Preparation of functional layer solution for laminated film 231> With reference to Example 3 of JP 2018-45220 A, the following components were mixed to obtain a functional layer solution for laminate film 231. Ethyl acetate (EA: boiling point 77°C) 100 parts by mass A-DCP 100 parts by mass Irgacure 127 2 parts by weight Leveling agent (F-784-F) 0.08 parts by weight

[0327] <Preparation of functional layer solution for laminated film 232> With reference to Example 3 of JP 2018-45220 A, the following components were mixed to obtain a functional layer solution for laminate film 232. Methylene chloride (boiling point 41°C) 900 parts by mass PSt: 70 parts by mass Polyarylate resin (compound P) 30 parts by mass Leveling agent (F-784-F) 0.08 parts by weight

[0328] <Preparation of functional layer solution for laminated film 233> With reference to Example 3 of JP 2018-41028 A, the following components were mixed to obtain a functional layer solution for laminate film 233. Ethyl acetate (EA: boiling point 77°C): 700 parts by mass PSt: 98 parts by mass Plasticizer (polyester compound) 2 parts by weight Leveling agent (F-784-F) 0.08 parts by weight

[0329] <Preparation of functional layer solution for laminated film 234> The following components were mixed to obtain a functional layer solution 234. Methylene chloride (boiling point 41°C): 800 parts by mass Ethanol (boiling point 78°C): 100 parts by mass TAC: 90 parts by mass Plasticizer (ethyl phthalyl ethyl glycolate): 10 parts by mass

[0330] [2] Preparation of laminated film <Preparation of Laminated Film 201> A PET film (TN100, base film A, manufactured by Toyobo Co., Ltd.) was prepared as a base film. A solution for the functional layer of the laminated film 201 was applied onto the release layer of this PET film using a die by a backcoat method, and then the laminated film was dried in the drying step described below to form a functional layer with a thickness of 5 μm, thereby obtaining the laminated film 201. 1st step: 1 min at 40℃ Second step: 70°C for 1 min 3rd step: 100℃ for 1 minute 4th step: 130℃ for 2 minutes

[0331] <Preparation of laminated films 202 to 234> Laminated films 202 to 234 were obtained in the same manner as in the production of laminated film 201, except that the type and thickness of the base film and the type and thickness of the functional layer solution were changed, as shown in Tables I to III. As for the drying temperature, only the dryer temperature in the fourth step was changed, and the temperatures in the first, second, and third steps were fixed.

[0332] Evaluation (1) Qualitative and quantitative analysis of residual solvents The residual solvent in the obtained laminated film was qualitatively and quantitatively analyzed by peeling the laminated film into the base film and the functional layer, and each was analyzed by headspace gas chromatography. In headspace gas chromatography, the sample was sealed in a container and heated, and the gas in the container was quickly injected into a gas chromatograph while the container was filled with volatile components, and mass analysis was performed to identify the compounds and to quantify the volatile components. The volatile components were quantitatively analyzed by creating a calibration curve in advance using samples with known concentrations, and comparing the peak area of ​​the volatile components obtained by measurement with the calibration curve.

[0333] (Measurement conditions) Head space device: HP7694 Head Space Sampler (manufactured by Hewlett-Packard) Temperature conditions: Transfer line 200℃, loop temperature 200℃ Sample volume: 0.8g / 20ml vial GC: HP5890 (Hewlett-Packard) MS:HP5971 (Hewlett-Packard) Column: HP-624 (30m x inner diameter 0.25mm) Oven temperature: initial temperature 40°C (holding time 3 minutes), heating rate 10°C / min, reaching temperature 200°C (holding time 5 minutes) Measurement mode: SIM (select ion monitor) mode

[0334] (2) Measurement of the humidity expansion coefficient (CHE2) of the functional layer at 23°C In the obtained laminated film, the humidity expansion coefficient at 23° C. (CHE2) of the functional layer was measured for a sample from which the base film had been peeled off in the same manner as for the humidity expansion coefficient of the above-mentioned base film (CHE1).

[0335] (3) Transportability (transport stability) The transport stability of the laminated film was evaluated by checking for the presence or absence of breakage or cracking when the film was transported on a line with rolls while applying a transport tension of 350 N / m. The transport stability was evaluated based on the following criteria. 〇: The functional layer can be transported without breaking. △: Small scratches and cracks occur in the functional layer, but transport is possible ×: The functional layer cracks and breaks. If it was rated as △ or better, it was judged to be good.

[0336] (4) Underwater curling The laminated film is cut into strips of 35 mm (horizontal direction at the time of manufacture) x 2 mm (vertical direction at the time of manufacture) and immersed in 38°C warm water for 30 minutes, after which the degree of curl in the width direction in water is measured. The measurement is made assuming that the side on which the functional layer is applied is concave.

[0337] [Curl degree] The obtained laminated film was cut into a circle with a diameter of 5 cm to be used as a sample. The obtained sample was left in a temperature- and humidity-controlled room at 23°C and 55% RH for 24 hours. The sample was then removed from the temperature- and humidity-controlled room and placed on a flat plate, and 1 / r was calculated using a curvature scale from the radius of curvature r (m) that had a curve matching the sample. The curl amount was then evaluated based on the following criteria. ◎: 1 / r is less than 4 ○: 1 / r is 4 or more and less than 8 △: 1 / r is 8 or more and less than 12 ×: 1 / r is 12 or more If it was rated △ or better, it was judged to be good.

[0338] (5) Adhesion to polarizers (Evaluation of adhesion) A 60μm-thick long polyvinyl alcohol film containing polyvinyl alcohol (hereinafter referred to as "PVA") was continuously conveyed through guide rolls and immersed in a dye bath (30°C) containing iodine and potassium iodide for dyeing and stretching by 2.5 times, and then stretched to a total of 5 times and crosslinked in an acid bath (60°C) containing boric acid and potassium iodide, and the resulting 12μm-thick iodine-PVA polarizer was dried in a dryer at 50°C for 30 minutes to obtain a polarizer with a moisture content of 4.9%. The polarizer was cut to 10cm x 10cm. Next, the following components were mixed to prepare water-based adhesive 1. Pure water: 100 parts by mass Polyvinyl alcohol resin (product name "GOHSEFYMER Z200" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.): 3 parts by weight Water-based adhesive 1 was applied to a PVA polarizer using a wire bar (#0), and the present film, processed to 10 cm x 10 cm, was laminated sheet-by-sheet using a high-precision tabletop laminating machine HAL-215 (manufactured by Sankyo Co., Ltd.) so that the functional layer surface was adhered to the PVA surface. The base film was then peeled off to produce a laminate of PVA and functional layer. The suitability of this laminate for the lamination process was evaluated as follows. (Evaluation rank) ◎: No air bubbles, bent edges, or film misalignment were observed even after laminating 50 sheets. ○: No air bubbles, bent edges, or film misalignment were observed even after laminating 20 sheets. △: No air bubbles, bent edges, or film misalignment were observed even after laminating 10 sheets. ×: After laminating 10 sheets, air bubbles, bent edges, misalignment of the film, etc. were observed in one or more sheets. (6) Interference fringes <Preparation of Polarizing Plate> Using the laminate films 201 to 234 prepared above, polarizing plates were prepared according to the following procedure.

[0339] (Preparation of polarizer) A long polyvinyl alcohol film with a thickness of 60 μm was continuously transported via guide rollers and immersed in a dye bath (30°C) containing iodine and potassium iodide for dyeing and stretching by 2.5 times. It was then stretched a total of 5 times and crosslinked in an acid bath (60°C) containing added boric acid and potassium iodide. The resulting iodine-PVA polarizer with a thickness of 12 μm was dried in a dryer at 50°C for 30 minutes to obtain a polarizer with a moisture content of 4.9%.

[0340] (Preparation of polarizing plate) The polarizers prepared above were sandwiched from both sides with laminate films 201-234 and the optical films described below as opposing films, and bonded via the water-soluble adhesive liquid 1 described below to prepare polarizing plates 201-234.

[0341] At that time, the longitudinal direction of the polarizer and the longitudinal axis of the laminated film were aligned with each other. <Facing film> The opposing film used was a film containing the following resin. COP (cycloolefin): JSR Corporation ARTON G7810 (Preparation of Water-Soluble Adhesive Solution 1) The following components were mixed and then degassed to prepare water-soluble adhesive solution 1.

[0342] Pure water 100 parts by mass Nippon Shokubai Co., Ltd. "Epocross WS-300" 7.5 parts by weight MENADIONA "CROSSLINKER CL-427" 0.1 part by mass The polarizing plate was prepared by subjecting the adhesive surface of the laminated film to a corona discharge treatment at a corona output intensity of 2.0 kW and a line speed of 18 m / min, applying the above-prepared water-soluble adhesive solution 1 to the corona discharge-treated surface using a bar coater so that the thickness after drying would be approximately 3 μm, and then drying at 50°C, 60°C, and 70°C in that order for 60 seconds each to obtain a polarizing plate. The prepared polarizing plate was placed on a black cloth such as a light-tight curtain with the side on which the functional layer was formed facing up, and illuminated with a three-wavelength fluorescent lamp (National fluorescent lamp: FL20SS ENW / 18, manufactured by Matsushita Electric Industrial Co., Ltd.). The surface of the polarizing plate was visually observed and evaluated according to the following criteria. ◎: Ten samples were observed and no interference unevenness was observed. ○: No interference fringes are visible △: interference fringes are faintly visible ×: Interference fringes are noticeable The manufacturing conditions for the obtained laminate films 201 to 234 are shown in Tables I, II and III, and the evaluation results are shown in Table 4. The content of the rubber particles indicates the mass % in the coating film (functional layer) after drying.

[0343] [Table 1]

[0344] [Table 2]

[0345] [Table 1]

[0346] [Table 2]

[0347] As shown in Table IV, the laminate films 201 to 208, 211 to 213, 216 to 218, 222, 224, and 226 to 229 of the present invention are superior overall to the laminate films of the comparative examples in terms of transportability, underwater curl, adhesion, and interference fringe evaluation. In particular, when the value shown by formula (1) is within the range of 0.30 to 1.00, adhesion is good, and when it is within the range of 0.40 to 0.80, the interference fringe characteristics tend to be further improved.

[0348] Example 2 The retardation of the functional layers of the laminated films 204, 213, 214, 216, 218, 226 and 229 produced in Example 1 was measured by the following method. The results are shown in Table V.

[0349] The retardations Ro and Rt were measured by the following method. 1) The substrate film is peeled off from the laminated film, and the functional layer is conditioned for 24 hours in an environment of 23°C and 55% RH. The average refractive index of this layer is measured with an Abbe refractometer, and the thickness d is measured with a commercially available micrometer. 2) After humidity conditioning, the retardation Ro and Rt of the film at a measurement wavelength of 590 nm are measured in an environment of 23° C. and 55% RH using an automatic birefringence meter Axoscan (Axo Scan Mueller Matrix Polarimeter, manufactured by Axometrics).

[0350] Ro and Rt are defined by the following formulas, respectively. Formula (a): Ro = (nx - ny) × d Formula (b): Rt = ((nx + ny) / 2 - nz) × d (In the formula, nx represents the refractive index of the functional layer in the in-plane slow axis direction, ny represents the refractive index of the functional layer in the direction perpendicular to the in-plane slow axis, nz represents the refractive index of the functional layer in the thickness direction, and d represents the thickness (nm) of the functional layer.)

[0351] [Table 3]

[0352] The results in Table V show that the retardation values ​​of the functional layer according to the present invention are Ro in the range of 0 to 20 nm and Rt in the range of -25 to 25 nm, both of which are suitable as retardation films for IPS mode liquid crystal display devices. [Industrial Applicability]

[0353] According to the present invention, a laminate film is obtained which, although thin, has excellent transportability and can be handled in the same way as conventional polarizing plate protective films, and further has excellent curl controllability during polarizing plate processing, so that it is possible to provide a high-quality polarizing plate and display device which has excellent productivity (bonding to a polarizer) during polarizing plate processing and is free of optical unevenness. [Explanation of symbols]

[0354] 1. Laminated film 2. Base film 3. Functional Layer 4 Adhesive layer 5 Polarizer 6 Opposing Film 10, 10' Polarizing plate B110 Base film B120 Functional Layer B200 manufacturing equipment B210 Supply section B220 Application unit B230 Drying section B240 Cooling section B250 Winding section

Claims

1. A laminated film in which a peelable functional layer is laminated on a base film, The base film contains polyethylene terephthalate, the functional layer contains a fumaric acid diester resin or a (meth)acrylic resin containing rubber particles, The thickness of the functional layer is within the range of 1 to 19 μm; The total thickness of the laminated film is 50 μm or less, The humidity expansion coefficient of the substrate film at 23° C. is CHE 1 (ppm / % RH), thickness is d 1 (μm), and the humidity expansion coefficient of the functional layer at 23° C. is CHE 2 (ppm / % RH), thickness is d 2 (μm), the laminate film satisfies the relationship of the following formula (1): Formula (1) 0.20 < │(CHE 1 -CHE 2 )│ × (d 2 / d 1 ) < 2.00

2. 2. The laminated film according to claim 1, wherein the functional layer has a thickness in the range of 2 to 10 μm.

3. 3. The laminate film according to claim 1, wherein the total thickness of the laminate film is within a range of 30 to 45 μm.

4. The retardation value Ro of the functional layer defined by the following formula (i) is in the range of 0 to 20 nm, and the retardation value Rt of the functional layer defined by the following formula (ii) is in the range of -25 to 25 nm. A laminate film according to any one of claims 1 to 3. Formula (i) Ro = (n x -n y ) x d Formula (ii) Rt={(n) x +n y ) / 2-. z }×d (In the above formulas (i) and (ii), Ro is the retardation value in the in-plane direction of the functional layer, Rt is the retardation value in the thickness direction of the functional layer, n x is the refractive index in the slow axis direction of the functional layer, n y is the refractive index in the fast axis direction in the plane of the functional layer, n z represents the refractive index in the thickness direction of the functional layer (the refractive index is measured at a wavelength of 590 nm under an environment of 23° C. and 55% RH), and d represents the thickness of the film (nm).

5. The content of the residual solvent in the base film is S 1 The residual solvent content of the functional layer is S 2 The laminate film according to any one of claims 1 to 4, characterized in that, when Formula (2) 10<S 1 <S 2 <1000(ppm)

6. 6. The laminate film according to claim 5, wherein a major residual solvent among the residual solvents has a boiling point of 100[deg.] C. or lower under atmospheric pressure.

7. 7. The laminate film according to claim 5, wherein the residual solvent is a chlorine-based solvent.

8. 8. The laminate film according to claim 5, wherein the residual solvent is dichloromethane.

9. 9. The laminate film according to claim 5, wherein the residual solvent comprises dichloromethane and alcohols.

10. The base film is a biaxially stretched polyester film, and the humidity expansion coefficient CHE of the polyester film at 23° C. 1 The laminate film according to any one of claims 1 to 9, characterized in that the humidity is within a range of 10 to 20 ppm / % RH.

11. 11. The laminate film according to claim 1, wherein the functional layer contains a polymer material having a carbonyl group on a side chain.

12. The laminate film according to any one of claims 1 to 10, characterized in that the functional layer contains a polymer material having a cyclic structure in its main chain.

13. A polarizing plate comprising the laminate film according to any one of claims 1 to 12.

14. A display device comprising the laminate film according to any one of claims 1 to 12 or the polarizing plate according to claim 13.

15. A method for producing a polarizing plate roll, comprising: laminating the laminate film according to any one of claims 1 to 12 to at least one surface of a polarizer while winding the laminate film, A method for producing a polarizing plate roll, comprising a step of winding up the laminate film while bonding the laminate film to the polarizer in the layered order from the inside of the roll: polarizer, adhesive layer, functional layer, and base film.

Citation Information

Patent Citations

  • Koatsukatsupuringusochi

    JP1976069215A

  • Laminate

    JP1993245995A

  • Optical film, optical compensation film, polarizing plate, liquid crystal display unit, and self luminous display unit

    JP2006293255A

  • Manufacturing method for transparent film

    JP2007045085A

  • Polarizing plate and liquid crystal display device

    JP2008107501A